Resin composition obtained by blending modified cellulose fiber, and method for manufacturing modified cellulose fiber
By reacting the cell loss fiber with the silane compound to form the modified fiber and mixing it with the resin, the problem of poor dispersion of the fiber in the resin is solved, and the thermal resistance and mechanical strength of the resin are improved.
Patent Information
- Application Number
- JP2024179821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2024-10-15
- Publication Date
- 2025-04-30
Smart Images

Figure 2025069095000001 
Figure 2025069095000002 
Figure 2025069095000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition containing modified cellulose fibers. The present invention further relates to a method for producing the modified cellulose fibers. [Background technology]
[0002] In recent years, electronic devices that handle large amounts of information at high speeds, such as digital home appliances, have become increasingly smaller, lighter, and thinner. This has created a demand for improved heat resistance and strength in the materials that make up electronic devices.
[0003] For example, cellulose nanofibers (CNFs) have excellent strength and are known to act as reinforcing materials when added in small amounts to composites with resins, etc. (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-241450 A Summary of the Invention [Problem to be solved by the invention]
[0005] Currently, there are various types of resins used in the components that make up electronic devices, each with different characteristics and properties. When cellulose fibers such as CNF are composited with resin, if the dispersibility in the resin is poor, aggregates may form, which may lead to a decrease in strength. The present invention relates to a method for producing modified cellulose fibers that can improve the heat resistance and strength of resins when blended with the resins. [Means for solving the problem]
[0006] The present invention relates to the following [1] to
[18] . [1] Modified cellulose fibers obtained by bonding cellulose fibers having modified groups other than silanol groups to silane compounds, and resin A resin composition comprising: [2] The resin composition according to [1], wherein the silane compound is one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. [3] The resin composition according to [1] or [2], wherein the amount of the silane compound is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group other than the silanol group is bonded. [4] The resin composition according to any one of the above [1] to [3], wherein the content of the modified cellulose in the resin composition is 4.0% by mass or more and 20% by mass or less. [5] The resin composition according to any one of the above [1] to [4], wherein the amount of the cellulose fiber in the resin composition is 0.1% by mass or more and 20% by mass or less. [6] The resin composition according to any one of the above [1] to [5], wherein the content of the resin in the resin composition is 70% by mass or more and 95% by mass or less. [7] The resin composition according to any one of [1] to [6], wherein the mass ratio of the amount of modified cellulose to the amount of resin in the resin composition (amount of modified cellulose fiber / amount of resin) is 5 / 95 or more and 20 / 80 or less. [8] The resin composition according to any one of the above [1] to [7], wherein a mass ratio of the amount of cellulose fiber to the amount of resin in the resin composition (amount of cellulose fiber / amount of resin) is 0.1 / 99.9 or more and 20 / 80 or less. [9] A resin molded product comprising the resin composition according to any one of [1] to [8] above.
[10] Step 1: A step of bonding a modifying group other than a silanol group to the ionic group of a cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 2: mixing the cellulose fiber having the modifying group bonded thereto with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. A method for producing modified cellulose fibers comprising: A method for producing modified cellulose fibers, wherein the amount of the silane compound blended in step 2 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded.
[11] Step 3: mixing cellulose fibers having ionic groups with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds to obtain cellulose fibers having silane compounds bonded thereto; and Step 4: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing modified cellulose fibers comprising: A method for producing modified cellulose fibers, wherein the amount of the silane compound blended in step 3 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the ionic group-containing cellulose fiber.
[12] A modified cellulose fiber produced by the production method described in
[10] or
[11] above.
[13] A composition comprising the modified cellulose fiber according to
[12] .
[14] The composition according to
[13] above, further comprising an organic solvent and / or a resin.
[15] A resin additive comprising the modified cellulose fiber according to
[12] .
[16] The resin additive according to
[15] above, further comprising an organic solvent.
[17] Step 5: A step of bonding a modifying group other than a silanol group to the ionic group of a cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 6: A step of mixing one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds, the cellulose fibers to which the modifying groups are bonded, and a resin. A method for producing a resin composition comprising: A method for producing a resin composition, wherein the amount of the silane compound blended in step 6 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded.
[18] Step 7: mixing cellulose fibers having ionic groups with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds to obtain cellulose fibers having silane compounds bonded thereto; and Step 8: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing a resin composition comprising: The method for producing a resin composition, wherein the amount of the silane compound blended in step 7 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber having an ionic group. Effect of the Invention
[0007] According to the present invention, a method for producing modified cellulose fiber that can improve the heat resistance and strength of a resin when blended with the resin can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The inventors have investigated the combination of resin, conventional modified cellulose fibers, and various other components, and have unexpectedly discovered that the heat resistance and mechanical strength of resins can be improved by bonding a specific silane compound, such as a silane compound that acquires silanol groups through hydrolysis, to cellulose fibers, thereby completing the present invention. The mechanism by which this effect occurs is unclear, but it is presumed to be as follows. That is, it was presumed that the functional groups in the resin that form crosslinks when the resin hardens react with the hydroxyl groups in the conventional modified cellulose fibers, thereby inhibiting crosslinking. Therefore, it is presumed that by reacting the hydroxyl groups in the conventional modified cellulose fibers with the silane compound in advance when the resin hardens, the inhibition of crosslinking by the hydroxyl groups can be reduced, and as a result, the heat resistance and mechanical strength of the resin can be achieved.
[0009] A. A method for producing modified cellulose fiber comprising steps 1 and 2 One embodiment of the method for producing the modified cellulose fiber of the present invention is Step 1: A step of bonding a modifying group other than a silanol group to an ionic group of a cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 2: mixing the cellulose fiber having the modifying group bonded thereto with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. A method for producing modified cellulose fibers comprising: The method for producing modified cellulose fibers, wherein the amount of the silane compound blended in step 2 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded.
[0010] [Cellulose fibers having ionic groups] The main properties of the "cellulose fibers having ionic groups" subjected to step 1 are as follows:
[0011] [Crystal structure] The cellulose fibers having ionic groups preferably have a cellulose I type crystal structure from the viewpoint of strength development of the resin after curing. The crystallinity of the cellulose fibers having ionic groups is preferably 10% or more, more preferably 15% or more, more preferably 20% or more, more preferably 30% or more, more preferably 40% or more, and more preferably 50% or more from the viewpoint of strength development of the resin after curing. In addition, from the viewpoint of raw material availability, it is preferably 90% or less, more preferably 85% or less, and more preferably 80% or less. In this specification, the crystallinity of various cellulose fibers is the cellulose I type crystallinity calculated from the diffraction intensity value by the X-ray diffraction method, and can be measured according to the method described in the Examples below. In addition, cellulose I type refers to the crystalline form of natural cellulose, and cellulose I type crystallinity refers to the proportion of the amount of crystalline regions in the entire cellulose fiber. The presence or absence of the cellulose I type crystal structure can be determined by the presence of a peak at 2θ=22.6° in X-ray diffraction measurement.
[0012] [Average fiber diameter] From the viewpoints of handleability, availability, and cost, the cellulose fibers having ionic groups have a diameter of preferably 1 μm or more, and more preferably 5 μm or more, and from the viewpoints of improving handleability and dispersibility, the diameter is preferably 300 μm or less, more preferably 100 μm or less, and even more preferably 60 μm or less.
[0013] [Average fiber length] The average fiber length of the cellulose fibers having ionic groups is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more from the viewpoint of strength expression of the cured resin, while it is preferably 500 μm or less, more preferably 400 μm or less, and even more preferably 300 μm or less from the viewpoint of handleability. The average fiber diameter and average fiber length of the cellulose fibers having an ionic group can be determined by the method described in the Examples below.
[0014] [Ionic group] Examples of the ionic group include anionic groups and cationic groups. Examples of the anionic group include a carboxy group, a sulfonic acid group, and a (phosphite) group, and examples of the cationic group include a group having an onium such as ammonium, phosphonium, or sulfonium in the group. The ionic group may be introduced alone or in combination of two or more kinds. From the viewpoint of efficiency of introduction into cellulose fibers, the ionic group is preferably an anionic group, and more preferably a carboxy group.
[0015] [Preparation of cellulose fibers having ionic groups] The "cellulose fibers having ionic groups" used in step 1 can be prepared by introducing desired ionic groups into the raw cellulose fibers.
[0016] [Cellulose fiber] As the cellulose fiber that is the raw material for the cellulose fiber having an ionic group, natural cellulose fibers are preferred from an environmental perspective, and examples thereof include wood pulp such as coniferous pulp and broadleaf pulp; cotton pulp such as cotton linter and cotton lint; non-wood pulp such as straw pulp and bagasse pulp; bacterial cellulose, etc., and these can be used alone or in combination of two or more.
[0017] The average fiber diameter of the raw cellulose fibers is not particularly limited, but from the viewpoints of handleability and cost, it is preferably 5 μm or more, more preferably 7 μm or more, and from the same viewpoints, it is preferably 500 μm or less, more preferably 300 μm or less. The average fiber diameter of the raw cellulose fibers is determined by the method described in the Examples below. The average fiber length of the raw cellulose fibers is not particularly limited, but from the viewpoints of availability and cost, it is preferably 5 μm or more, more preferably 25 μm or more, and from the same viewpoints, it is preferably 5,000 μm or less, more preferably 3,000 μm or less. The average fiber length of the raw cellulose fibers can be measured according to the method described in the Examples below.
[0018] [Method of introducing ionic groups] Methods for introducing ionic groups, for example carboxy groups as anionic groups, into cellulose fibers include a method of oxidizing hydroxy groups of the cellulose fibers to convert them to carboxy groups, and a method of reacting the hydroxy groups of the cellulose fibers with at least one selected from the group consisting of compounds having a carboxy group, acid anhydrides of compounds having a carboxy group, and derivatives thereof. In this specification, cellulose fibers into which anionic groups have been introduced are referred to as "anion-modified cellulose fibers."
[0019] Examples of methods for oxidizing the hydroxyl groups of cellulose fibers include a method described in JP 2015-143336 A or JP 2015-143337 A in which an oxidizing agent such as sodium hypochlorite and a bromide such as sodium bromide are reacted with the raw cellulose fibers using 2,2,6,6-tetramethyl-1-piperidine-N-oxyl (TEMPO) as a catalyst.
[0020] By oxidizing cellulose fibers using TEMPO as a catalyst, the hydroxymethyl group at C6 in the glucose unit constituting the cellulose fiber is selectively converted to a carboxy group. Such fibers in which the hydroxymethyl group at C6 in the glucose unit is selectively converted to a carboxy group are called "TEMPO oxidized cellulose fibers." TEMPO oxidized cellulose fibers are a suitable example of the cellulose fiber having an ionic group in the present invention.
[0021] [Carboxy group content] The ionic group content, i.e., the carboxy group content, in the TEMPO-oxidized cellulose fiber is preferably 0.1 mmol / g or more, more preferably 0.4 mmol / g or more, even more preferably 0.6 mmol / g or more, even more preferably 0.7 mmol / g or more, and even more preferably 0.8 mmol / g or more, from the viewpoint of stable introduction of a modifying group. Moreover, from the viewpoint of improving the handleability, it is preferably 3 mmol / g or less, more preferably 2.5 mmol / g or less, even more preferably 2 mmol / g or less, even more preferably 1.9 mmol / g or less, and even more preferably 1.8 mmol / g or less. The "carboxy group content" means the total amount of carboxy groups in the glucose moiety constituting the cellulose fiber, and is specifically measured by the method described in the Examples below.
[0022] [Process 1] Step 1 in the present invention is a step of bonding a modifying group other than a silanol group to the ionic group of a cellulose fiber having an ionic group, thereby obtaining a cellulose fiber to which the modifying group is bonded.
[0023] [Modification groups other than silanol groups] Specific examples of the "modifying group other than a silanol group" in the present invention include (a) a hydrocarbon group and (b) a polymer group. One type of these modifying groups is bonded (introduced) to the ionic groups of the cellulose fibers having ionic groups, either alone or in combination. The bonding mode between the modifying group and the ionic group includes an ionic bond and / or a covalent bond. Examples of the covalent bond include an amide bond, an ester bond, and a urethane bond.
[0024] (a) Hydrocarbon group The hydrocarbon group includes monovalent hydrocarbon groups, for example, chain saturated hydrocarbon groups, chain unsaturated hydrocarbon groups, cyclic saturated hydrocarbon groups, and (heterocyclic) aromatic hydrocarbon groups. The number of carbon atoms in the hydrocarbon group is 1 or more, preferably 3 or more, more preferably 8 or more, and even more preferably 10 or more, and is preferably 30 or less, more preferably 22 or less, and even more preferably 18 or less. The hydrocarbon group may have a substituent described later, and a part of the hydrocarbon group may be substituted with a hydrogen nitride group.
[0025] Specific examples of chain saturated hydrocarbon groups include methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, tert-butyl, isobutyl, pentyl, tert-pentyl, isopentyl, hexyl, isohexyl, heptyl, octyl, 2-ethylhexyl, nonyl, decyl, dodecyl, tridecyl, trioctyl, tetradecyl, octadecyl, docosyl, and octacosanyl groups.
[0026] Specific examples of the chain unsaturated hydrocarbon group include an ethylene group, a propylene group, a butene group, an isobutene group, an isoprene group, a pentene group, a hexene group, a heptene group, an octene group, a nonene group, a decene group, a dodecene group, a tridecene group, a tetradecene group, and an octadecene group.
[0027] Specific examples of cyclic saturated hydrocarbon groups include cyclopropane, cyclobutyl, cyclopentane, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cyclododecyl, cyclotridecyl, cyclotetradecyl, and cyclooctadecyl groups.
[0028] The aromatic hydrocarbon group is, for example, selected from the group consisting of an aryl group and an aralkyl group.
[0029] Examples of the aryl group include a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, a biphenyl group, a triphenyl group, a terphenyl group, and groups in which these groups are substituted with the substituents described below.
[0030] Examples of the aralkyl group include a benzyl group, a dibenzyl group, a trityl group, a phenethyl group, a phenylpropyl group, a phenylpentyl group, a phenylhexyl group, a phenylheptyl group, a phenyloctyl group, and groups in which the aromatic group of these groups is further substituted with a substituent.
[0031] (b) Polymer group The polymer group is a functional group containing a polymer structure. From the viewpoint of improving dispersion stability, the molecular weight of the polymer group is preferably 100 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, even more preferably 600 or more, even more preferably 1,000 or more, and even more preferably 1,500 or more. From the same viewpoint, it is preferably 10,000 or less, more preferably 7,000 or less, even more preferably 5,000 or less, even more preferably 4,000 or less, even more preferably 3,500 or less, and even more preferably 2,500 or less.
[0032] From the viewpoint of improving dispersion stability, the polymer group is preferably a functional group having a repeating structure linked by a structure having an oxygen atom, more preferably a functional group having a repeating structure linked by an oxygen atom, such as a polyoxyalkylene structure (alkylene oxide chain) or a polysiloxane structure (silicone chain), more preferably a functional group having a polyoxyalkylene structure, and even more preferably an alkoxypolyoxyalkylene group.
[0033] (b-1) Polysiloxane structure (silicone chain) The polysiloxane structure (silicone chain) is a structure having a siloxane bond as the main chain, which may further include an alkylene group. The polysiloxane structure may have a substituent, which will be described later.
[0034] (b-2) Polyoxyalkylene structure (alkylene oxide chain) From the viewpoint of improving dispersion stability, the polyoxyalkylene structure (alkylene oxide chain) is preferably a (co)polymer structure of one or more oxyalkylenes selected from oxyalkylenes having 2 to 8 carbon atoms, more preferably a (co)polymer structure of one or more oxyalkylenes selected from oxyalkylenes having 2 to 4 carbon atoms, even more preferably a (co)polymer structure of one or two oxyalkylenes selected from ethylene oxide (EO) and propylene oxide (PO), and even more preferably a copolymer structure in which ethylene oxide (EO) and propylene oxide (PO) are polymerized randomly or in a block form (also referred to as an (EO / PO) structure).
[0035] The polyoxyalkylene structure may, for example, be one represented by the following formula:
[0036] [ka]
[0037] (In the formula, R 1 represents a hydrogen atom, a hydrocarbon group having 1 to 6 carbon atoms, or a -CH2CH(CH3)NH2 group. EO and PO are present randomly or in a block form, a is 0 or a positive number indicating the average number of moles of EO added, and b is 0 or a positive number indicating the average number of moles of PO added. However, a and b cannot be 0 at the same time. ) are examples of groups represented by the formula:
[0038] R 1 When R is a linear or branched alkyl group having 1 to 6 carbon atoms, the alkyl group is preferably a methyl group, an ethyl group, an n-propyl group, or a sec-propyl group. 1 may be a hydrogen atom.
[0039] From the viewpoint of improving dispersion stability, a is preferably 0 or more, more preferably 1 or more, even more preferably 3 or more, even more preferably 6 or more, even more preferably 11 or more, even more preferably 15 or more, even more preferably 20 or more, even more preferably 25 or more, and even more preferably 30 or more. From the same viewpoint, a is preferably 100 or less, more preferably 70 or less, even more preferably 60 or less, even more preferably 50 or less, and even more preferably 40 or less.
[0040] From the viewpoint of improving dispersion stability, b is preferably 0 or more, more preferably 1 or more, even more preferably 3 or more, and even more preferably 5 or more. From the same viewpoint, b is preferably 50 or less, more preferably 40 or less, even more preferably 30 or less, even more preferably 25 or less, even more preferably 20 or less, even more preferably 15 or less, and even more preferably 10 or less.
[0041] In the above formula, a+b represents the average total number of moles of EO and PO added, and is preferably 4 or more, more preferably 6 or more, and more preferably 8 or more, and from the same viewpoint, is preferably 100 or less, and more preferably 70 or less.
[0042] Examples of the alkylene group having 1 to 3 carbon atoms include a methylene group, an ethylene group, and a propylene group.
[0043] The PO content (mol%) in the (EO / PO) chain can be calculated based on the above a and b, specifically, it can be obtained by b×100 / (a+b). From the viewpoint of further improving dispersibility, the PO content is preferably 1 mol% or more, more preferably 5 mol% or more, even more preferably 7 mol% or more, and even more preferably 10 mol% or more. From the same viewpoint, it is preferably 100 mol% or less, more preferably 90 mol% or less, even more preferably 85 mol% or less, even more preferably 75 mol% or less, even more preferably 60 mol% or less, even more preferably 50 mol% or less, even more preferably 40 mol% or less, and even more preferably 30 mol% or less.
[0044] From the viewpoint of improving dispersion stability, the formula weight (molecular weight) of the polyoxyalkylene structure is preferably 100 or more, more preferably 200 or more, even more preferably 300 or more, even more preferably 500 or more, even more preferably 1,000 or more, and even more preferably 1,500 or more. From the same viewpoint, it is preferably 10,000 or less, more preferably 7,000 or less, even more preferably 5,000 or less, even more preferably 4,000 or less, even more preferably 3,500 or less, and even more preferably 2,500 or less.
[0045] (c) Further Substituents The modifying group may further have a substituent, for example, an alkoxy group having 1 to 6 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a sec-butoxy group, a tert-butoxy group, a pentyloxy group, an isopentyloxy group, or a hexyloxy group; a methoxycarbonyl group, an ethoxycarbonyl group, a propoxycarbonyl group, an isopropoxycarbonyl group, a butoxycarbonyl group, an isobutoxycarbonyl group, a sec-butoxycarbonyl group, or a hexyloxy group; groups, alkoxy-carbonyl groups having 1 to 6 carbon atoms, such as a tert-butoxycarbonyl group, a pentyloxycarbonyl group, or an isopentyloxycarbonyl group; halogen atoms, such as a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom; acyl groups having 1 to 6 carbon atoms, such as an acetyl group or a propionyl group; aralkyl groups; aralkyloxy groups; alkylamino groups having 1 to 6 carbon atoms; dialkylamino groups having an alkyl group with 1 to 6 carbon atoms; and a hydroxy group.
[0046] [Method of bonding modifying groups other than silanol groups] Step 1 can be carried out by mixing cellulose fibers having an ionic group with a compound having a modifying group other than the above-mentioned silanol group (referred to as a "modifying compound" in this specification) to react the two. As a specific method for step 1, a known method, for example, the method described in JP 2015-143336 A, can be used. According to this method, the modifying group and the ionic group are bonded by an ionic bond. Alternatively, step 1 can also be carried out by the method described in JP 2015-143337 A, for example. In this case, the modifying group and the ionic group are bonded by an amide bond.
[0047] (Modification compound) From the viewpoint of improving dispersion stability, the modifying compound may be a compound that has a modifying group other than a silanol group and is capable of bonding to cellulose fibers having an ionic group. When TEMPO-oxidized cellulose fibers are used as the cellulose fibers having an ionic group, the modifying compound is preferably a compound having a modifying group and a cationic group, more preferably a compound having a modifying group and an amino group or a quaternary ammonium group. From the viewpoint of improving dispersion stability, preferred examples of the modifying compound include amine compounds having a modifying group and at least one amino group in the molecule, more specifically, amine compounds having a hydrocarbon group, amine compounds having a polysiloxane structure, amine compounds having a polyoxyalkylene structure, etc.
[0048] Such an amine compound may be any of primary amines, secondary amines, tertiary amines, and quaternary ammonium compounds. From the viewpoint of reactivity, preferred anion components of the quaternary ammonium compounds include halogen ions such as chloride ions and bromide ions, hydrogen sulfate ions, perchlorate ions, tetrafluoroborate ions, hexafluorophosphate ions, trifluoromethanesulfonate ions, and hydroxy ions.
[0049] (a) Amine compounds having a hydrocarbon group Specific examples of the amine compound having a hydrocarbon group include primary to tertiary amines such as ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, dibutylamine, hexylamine, 2-ethylhexylamine, dihexylamine, trihexylamine, octylamine, dioctylamine, trioctylamine, dodecylamine, didodecylamine, stearylamine, distearylamine, monoethanolamine, diethanolamine, triethanolamine, oleylamine, aniline, octadecylamine, dimethylbehenylamine, benzylamine, dibenzylamine, tritylamine, naphthylamine, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, and 1-(3-aminopropyl)imidazole.
[0050] Examples of quaternary ammonium compounds include tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetraethylammonium chloride, tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), tetrabutylammonium chloride, lauryltrimethylammonium chloride, dilauryldimethyl chloride, stearyltrimethylammonium chloride, distearyldimethylammonium chloride, cetyltrimethylammonium chloride, and alkylbenzyldimethylammonium chloride.
[0051] The amine compound having a hydrocarbon group may be a commercially available product or may be prepared according to a known method.
[0052] The hydrocarbon compound having a cationic group may have a substituent. Specific examples of the substituent include those described above in "(c) Further Substituents."
[0053] (b-1) Amine compound having a polysiloxane structure Such amine compounds include, for example, those having a structure in which an amino group is bonded to the backbone of a polysiloxane structure via an alkylene group or the like. In this specification, such amine compounds may be referred to as "amino-modified silicone". The amino-modified silicone may be a commercially available product or may be prepared according to a known method. Only one type of amino-modified silicone may be used, or two or more types may be used.
[0054] As amino-modified silicones, from the viewpoint of performance, the following products are recommended: TSF4703 (kinetic viscosity: 1000, amino equivalent: 1600), TSF4708 (kinetic viscosity: 1000, amino equivalent: 2800) manufactured by Momentive Performance Materials, SS-3551 (kinetic viscosity: 1000, amino equivalent: 1600), SF8457C (kinetic viscosity: 1200, amino equivalent: 1800), SF8417 (kinetic viscosity: 1200, amino equivalent: 1700), BY16-209 (kinetic viscosity: 500, amino equivalent: 1800), B Preferred are Y16-892 (kinetic viscosity: 1500, amino equivalent: 2000), BY16-898 (kinetic viscosity: 2000, amino equivalent: 2900), FZ-3760 (kinetic viscosity: 220, amino equivalent: 1600), KF8002 (kinetic viscosity: 1100, amino equivalent: 1700), KF867 (kinetic viscosity: 1300, amino equivalent: 1700), KF-864 (kinetic viscosity: 1700, amino equivalent: 3800), BY16-213 (kinetic viscosity: 55, amino equivalent: 2700), and BY16-853U (kinetic viscosity: 14, amino equivalent: 450) manufactured by Shin-Etsu Chemical Co., Ltd. In parentheses, the kinetic viscosity is the value measured at 25°C (unit: mm 2 / s) and the unit of amino equivalent is g / mol.
[0055] (b-2) Amine compound having a polyoxyalkylene structure In the amine compound, the polyoxyalkylene structure and the nitrogen atom of the amine compound are preferably bonded directly or via a linking group. The linking group is preferably a hydrocarbon group, and includes an alkylene group having a carbon number of preferably 1 to 6, more preferably 1 to 3. As such an alkylene group, for example, an ethylene group or a propylene group is preferable.
[0056] Examples of the amine compound having a polyoxyalkylene structure include those represented by the following formula (i):
[0057] [ka]
[0058] In the formula (i), R 1 In the formula, a and b are each an example of the polyoxyalkylene structure. 1 , a and b. The amine compound having a polyoxyalkylene structure is a compound for introducing a modifying group represented by the polyoxyalkylene structure, and can be prepared according to a known method. For example, a desired amount of ethylene oxide and propylene oxide can be added to a propylene glycol alkyl ether, and then the hydroxyl group terminal can be aminated. If necessary, the alkyl ether can be cleaved with an acid to make the terminal a hydrogen atom. For the manufacturing method thereof, refer to JP-A-3-181448, and the details of such an amine compound are described, for example, in JP-A-6105139.
[0059] As the amine compound having a polyoxyalkylene structure, for example, a commercially available product can be suitably used. Specific examples of the amine compound having an EO chain or a PO chain and which may have a hydrocarbon group include SUNBRIGHT MEPA-10H, SUNBRIGHT MEPA-20H, SUNBRIGHT MEPA-50H, SUNBRIGHT MEPA-10T, SUNBRIGHT MEPA-12T, SUNBRIGHT MEPA-20T, SUNBRIGHT MEPA-30T, SUNBRIGHT MEPA-40T, and the like, manufactured by NOF Corporation.
[0060] Specific examples of the amine compound having an EO / PO chain and which may have a hydrocarbon group include Jeffamine M-2070, Jeffamine M-2005, Jeffamine M-2095, Jeffamine M-1000, Jeffamine M-600, Surfoamine B200, Surfoamine L100, Surfoamine L200, Surfoamine L207, Surfoamine L300, Surfoamine B-100, XTJ-501, XTJ-506, XTJ-507, XTJ-508, M3000, Jeffamine ED-600, Jeffamine ED-900, Jeffamine ED-2003, Jeffamine D-230, Jeffamine D-400, Jeffamine D-2000, Jeffamine D-4000, XTJ-510, Jeffamine T-3000, Jeffamine T-5000, XTJ-502, XTJ-509, XTJ-510, etc. These may be used alone or in combination of two or more.
[0061] (Mixed condition) The temperature during mixing, i.e., the reaction temperature, is less than 25° C., preferably 20° C. or less, more preferably 10° C. or less, from the viewpoint of reactivity. Also, from the viewpoint of the product yield, it is preferably −20° C. or more, more preferably −10° C. or more, preferably −5° C. or more.
[0062] The mixing time is preferably 0.1 hours or more, more preferably 0.5 hours or more, and even more preferably 1 hour or more, and from the viewpoint of productivity, is preferably 120 hours or less, more preferably 72 hours or less, even more preferably 48 hours or less, and even more preferably 24 hours or less.
[0063] A solvent can be used for the mixing in step 1. As the solvent, it is preferable to select a solvent in which the compound to be used dissolves, and examples thereof include methanol, ethanol, isopropanol (IPA), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), N,N-dimethylacetamide, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), cyclohexanone, ethyl acetate, acetonitrile, dichloromethane, chloroform, toluene, acetic acid, 1-methoxy-2-propanol (PGME), water, etc., and these can be used alone or in combination of two or more. Furthermore, in order to disperse each component more uniformly in step 1, a dispersion treatment using a high-pressure homogenizer or the like may be carried out after mixing is completed.
[0064] A condensing agent can be used for the mixing in step 1. By using the condensing agent, the modifying group and the ionic group can be bonded by an amide bond. The condensing agent is not particularly limited, but includes those described in Synthetic Chemistry Series: Peptide Synthesis (Maruzensha), p. 116, and those described in Tetrahedron, 57, 1551, (2001), and examples thereof include 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride.
[0065] (Amount of modifying compound used) The amount of the modifying compound used in step 1 is preferably within the following range, for example. That is, the range of the amount used can be shown as the range of equivalents of the functional group (which can react with the ionic group) of the modifying compound used relative to the ionic group of the cellulose fiber having the ionic group, and specifically, from the viewpoint of improving the dispersion stability, it is preferably 0.10 equivalents or more, more preferably 0.15 equivalents or more, and even more preferably 0.2 equivalents or more. Also, from the viewpoint of film-forming property, it is preferably 20 equivalents or less, more preferably 5 equivalents or less, even more preferably 1 equivalent or less, and even more preferably 0.7 equivalents or less.
[0066] [Cellulose fibers with modified groups] The main properties of the cellulose fibers having modifying groups attached thereto obtained in step 1 are as follows: (Average fiber diameter) The cellulose fibers having a modified group bonded thereto are preferably those that have been subjected to a micronization treatment to have a nanometer size. Therefore, the average fiber diameter of the cellulose fibers having a modified group bonded thereto is preferably 1 nm or more, more preferably 2 nm or more, from the viewpoints of handling, availability, and cost, and is preferably 300 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 120 nm or less, from the viewpoints of improving handling and dispersibility.
[0067] (average fiber length) The average fiber length of the cellulose fibers to which modifying groups are bonded is preferably 10 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more from the viewpoint of strength expression of the resin after curing, while it is preferably 1000 nm or less, more preferably 500 nm or less, and even more preferably 300 nm or less from the viewpoint of ejection property and handling property. The average fiber diameter and average fiber length of the cellulose fibers having a modifying group bonded thereto can be determined by the method described in the Examples below.
[0068] (Modification group binding amount and introduction rate) The amount of the modifying groups bound to the cellulose fibers is preferably 0.01 mmol / g or more from the viewpoint of affinity with the resin component, and from the same viewpoint, is preferably 3.0 mmol / g or less. When any two or more types of modifying groups are simultaneously introduced into the cellulose fibers as the modifying groups, it is preferable that the total amount of the modifying groups bound is within the above range.
[0069] From the viewpoint of dispersibility, the introduction rate of the modifying groups in the cellulose fibers to which the modifying groups are bonded is preferably 10 mol% or more, the higher the better, and is preferably 100 mol%. When any two or more types of modifying groups are simultaneously introduced as the modifying groups, it is preferable that the total introduction rate is within the above range, provided that it does not exceed the upper limit of 100 mol%.
[0070] The bonded amount and introduction rate of the modifying group can be adjusted by the type and amount of the modifying compound added, the reaction temperature, the reaction time, the type of the solvent, etc. The bonded amount (mmol / g) and introduction rate (mol%) of the modifying group refer to the amount and ratio of the modifying group introduced (bonded) to the ionic group in the cellulose fiber to which the modifying group is bonded. For example, when the ionic group is a carboxy group, the bonded amount and introduction rate of the modifying group in the cellulose fiber to which the modifying group is bonded are calculated by the method described in the Examples below.
[0071] [Process 2] Step 2 in the present invention is a step of mixing the cellulose fibers having modified groups bonded thereto obtained in step 1 with a specific silane compound, i.e., one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. It is presumed that by mixing, at least a portion of the functional groups of the silane compound are converted to silanol groups, and at least a portion of these silanol groups react with at least a portion of the hydroxyl groups of the cellulose fibers to which the modifying groups are bonded, thereby bonding the silane compound to the cellulose fibers to which the modifying groups are bonded.
[0072] [Silane compounds]The silane compound used in this step is one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. Specifically, chlorosilane compounds such as tetrachlorosilane, methyltrichlorosilane, phenyltrichlorosilane, dimethyldichlorosilane, diphenyldichlorosilane, methylvinyldichlorosilane, trimethylchlorosilane, and methyldiphenylchlorosilane; tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, tetrabutoxysilane, methyltrimethoxysilane, methyltriethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, hexadecyltrimethoxysilane, polyethylene glycol-modified alkoxysilane, trimethoxyvinylsilane, triethoxyvinylsilane, 7-octenyltrimethoxysilane, n-propyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, [8-(glycidyloxy)-n-octyl]trimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxy, 8-methacryloxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-chloropropylmethyldimethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane silane, dimethoxydiethoxysilane, trimethylmethoxysilane, trimethylethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-aminopropyldiethoxymethylsilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, [3-(methylamino)propyl]trimethoxysilane, [3-(butylamino)propyl]trimethoxysilane, N-[3-(trimethoxysilyl)propyl]hexamethylenediamine, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N,Examples of the silane compounds include alkoxysilane compounds such as N-dimethyl-3-(trimethoxysilyl)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, and 3-ureidopropyltrialkoxysilane; acetoxysilane compounds such as tetraacetoxysilane, methyltriacetoxysilane, phenyltriacetoxysilane, dimethyldiacetoxysilane, diphenyldiacetoxysilane, and trimethylacetoxysilane; and silanol compounds such as dimethylsilanediol, diphenylsilanediol, and trimethylsilanol. Among the above-listed silane compounds, alkoxysilane compounds are preferred from the viewpoints of availability and reactivity. More preferred examples of such silane compounds include 3-aminopropyltrimethoxysilane, n-propyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane.
[0073] [Mixing conditions] The temperature during mixing, i.e., the reaction temperature, is preferably 70° C. or lower, more preferably 50° C. or lower, and even more preferably 30° C. or lower, from the viewpoint of suppressing the condensation reaction between the silane compounds. Also, from the viewpoint of the yield of the modified cellulose fiber, the temperature is preferably −20° C. or higher, more preferably −10° C. or higher, and preferably −5° C. or higher. The mixing time is preferably 0.1 hours or more, more preferably 0.5 hours or more, and even more preferably 1 hour or more, and from the viewpoint of productivity, is preferably 120 hours or less, more preferably 72 hours or less, even more preferably 48 hours or less, and even more preferably 24 hours or less.
[0074] A solvent can be used for the mixing in step 2. As the solvent, it is preferable to select a solvent in which the compound to be used dissolves, and examples thereof include methanol, ethanol, isopropanol (IPA), N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), N,N-dimethylacetamide, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), cyclohexanone, ethyl acetate, acetonitrile, dichloromethane, chloroform, toluene, acetic acid, 1-methoxy-2-propanol (PGME), water, etc., and these can be used alone or in combination of two or more. Furthermore, in order to disperse each component more uniformly in step 2, a dispersion treatment using a high-pressure homogenizer or the like may be carried out after mixing is completed.
[0075] (Silane compound content) The amount of the silane compound in step 2 is 50 parts by mass or more relative to 100 parts by mass of the cellulose fibers having modified groups bonded thereto. Here, the mass of the cellulose fibers having modified groups bonded thereto refers to the mass of only the cellulose fiber portion in the cellulose fibers having modified groups bonded thereto, i.e., the mass of the cellulose fiber portion excluding the modifying groups from the cellulose fibers having modified groups bonded thereto. From the viewpoint of improving the heat resistance of a resin when blended with the silane compound, the blending amount of the silane compound is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more. On the other hand, from the viewpoint of cost, the blending amount of the silane compound is preferably 1,000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 500 parts by mass or less.
[0076] [Refining process] By micronizing the cellulose fibers at any stage of the production method of the present invention, it is possible to micronize the cellulose fibers from the micrometer scale to the nanometer scale. By reducing the average fiber diameter to the nanometer size, the dispersibility in the resin is improved, which is preferable.
[0077] The micronization treatment can be carried out by a known micronization treatment method. For example, when obtaining modified cellulose fibers having an average fiber diameter of nanometer size, a treatment method using a grinder such as a mass colloider or a treatment method using a high-pressure homogenizer in a medium may be carried out. Specific examples of media and devices used in the micropatterning process are described in paragraphs 0079 to 0080 of JP 2022-001634 A.
[0078] [Short fiber processing] At any stage of the production method of the present invention, the cellulose fibers may be further subjected to a fiber shortening treatment, i.e., a treatment for shortening the fiber length. The fiber shortening treatment can be achieved by subjecting the target cellulose fibers to a known treatment, for example, one or more treatment methods selected from the group consisting of alkali treatment, acid treatment, heat treatment, ultraviolet treatment, electron beam treatment, mechanical treatment, and enzyme treatment.
[0079] B. Method for producing modified cellulose fiber comprising steps 3 and 4 A further aspect of the method for producing modified cellulose fibers of the present invention is Step 3: mixing cellulose fibers having ionic groups with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds to obtain cellulose fibers to which the silane compounds are bonded; and Step 4: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing modified cellulose fibers comprising: The method for producing modified cellulose fibers, wherein the amount of the silane compound blended in step 3 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the ionic group-containing cellulose fiber.
[0080] [Step 3] Step 3 in the present invention is a step of mixing cellulose fibers having ionic groups with the above-mentioned specific silane compound to obtain cellulose fibers to which the silane compound is bonded. It is presumed that, by mixing, at least a part of the functional groups of the silane compound is converted to silanol groups, and at least a part of the silanol groups reacts with at least a part of the hydroxyl groups of the cellulose fibers having ionic groups, thereby bonding the silane compound to the cellulose fibers. It is also presumed that the ionic groups in the cellulose fibers having ionic groups do not react with the silanol groups.
[0081] [Cellulose fibers with ionic groups] The main properties of the "cellulose fibers having ionic groups" subjected to step 3 are the same as those in embodiment A above.
[0082] [Preparation of cellulose fibers with ionic groups] The method for preparing the "cellulose fibers having ionic groups" in step 3 is the same as that in embodiment A above.
[0083] [Silane compounds] The "silane compound" used in step 3 is the same as that in embodiment A above.
[0084] [Mixing conditions] The mixing temperature, mixing time, and solvent that can be used during mixing are the same as those in the above step 2. Furthermore, in order to disperse each component more uniformly in step 3, a dispersion treatment using a high-pressure homogenizer or the like may be performed after the mixing is completed.
[0085] (Silane compound content) The amount of the silane compound in step 3 is 50 parts by mass or more per 100 parts by mass of the cellulose fibers having ionic groups. Here, the mass of the cellulose fibers having ionic groups refers to the mass of only the cellulose fiber portion in the cellulose fibers having ionic groups, i.e., the mass of the cellulose fiber portion excluding the ionic groups from the cellulose fibers having ionic groups. From the viewpoint of improving the heat resistance of a resin when blended with the silane compound, the blending amount of the silane compound is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more. On the other hand, from the viewpoint of cost, the blending amount of the silane compound is preferably 1,000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 500 parts by mass or less.
[0086] [Cellulose fibers bonded with silane compounds] The main properties of the cellulose fibers having the silane compound bonded thereto obtained in step 3, such as the average fiber diameter and the average fiber length, are the same as those of the "cellulose fibers having a modifying group bonded thereto" obtained in step 1 above.
[0087] [Step 4] Step 4 is a step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded.
[0088] The "modifying group other than a silanol group" introduced in step 4 is the same as that in embodiment A above. The "method of bonding a modifying group other than a silanol group" in step 4, the "modifying compound" and "amount used" used, the "mixing conditions" during bonding, the "bonding amount and introduction rate of the modifying group", and the like are the same as those in the above-mentioned embodiment A.
[0089] At any stage of the production process of this embodiment, the cellulose fibers may be subjected to a fine fiber refining treatment and / or a short fiber refining treatment, as in the above-mentioned embodiment A.
[0090] C. Modified cellulose fiber produced by the above-mentioned production method of A or B Aspect C of the present invention is a modified cellulose fiber produced by the production method of Aspect A or B above. As described above, the modified cellulose fiber can be obtained by the production method including steps 1 and 2, or by the production method including steps 3 and 4. At least a portion of the modified cellulose fiber is bonded to the silane compound.
[0091] It is presumed that by mixing in step 2 or step 3, at least a portion of the functional groups of the silane compound are converted to silanol groups, and at least a portion of these silanol groups react with at least a portion of the hydroxy groups of the cellulose fibers to which the modifying groups are bonded or at least a portion of the hydroxy groups of the cellulose fibers having ionic groups, thereby bonding the silane compound to the cellulose fibers. Thus, the modified cellulose fibers produced by the production method of aspect A or the production method of aspect B have modifying groups and groups derived from the silane compound.
[0092] The preferred contents of the respective components in the modified cellulose fiber of the present invention are as follows. The cellulose fiber content, i.e., the amount of the cellulose fiber portion excluding the bound modifying groups and the bound silane compounds, is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 90 mass% or less, more preferably 80 mass% or less, and even more preferably 70 mass% or less.
[0093] From the viewpoint of improving the heat resistance of the resin, the content of the silane compound is preferably 1 mass% or more, more preferably 5 mass% or more, and even more preferably 10 mass% or more, while from the same viewpoint, it is preferably 80 mass% or less, more preferably 70 mass% or less, and even more preferably 60 mass% or less.
[0094] From the viewpoint of improving the heat resistance of the resin, the content of the modifying group is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 5% by mass or more, while from the same viewpoint, it is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less.
[0095] The content of each component can be calculated from the blended amount of each component.
[0096] D. Compositions Containing Modified Cellulosic Fibers Aspect D of the present invention is a composition containing modified cellulose fibers. The composition of the present invention includes modified cellulose fibers and may further include an organic solvent and / or a resin.
[0097] [Organic solvent] As the organic solvent, it is preferable to select a solvent in which the modified cellulose fiber and the silane compound are soluble. Examples of the organic solvent include methanol, ethanol, isopropanol (IPA), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), cyclohexanone, ethyl acetate, acetonitrile, dichloromethane, chloroform, toluene, acetic acid, 1-methoxy-2-propanol (PGME), and the like. These can be used alone or in combination of two or more.
[0098] When the composition of the present invention contains an organic solvent, the preferred contents of the respective components are as follows. The content of cellulose fibers in the composition of the present invention, i.e., the amount of the cellulose fiber portion excluding the bound modifying groups and the bound silane compounds, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less.
[0099] The content of the silane compound in the composition of the present invention, i.e., the total amount of the silane compound bonded to the modified cellulose fiber and the silane compound not bonded to the modified cellulose fiber, is preferably 0.03 mass% or more, more preferably 0.15 mass% or more, and even more preferably 0.3 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 40 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less.
[0100] The content of the modifying group in the composition of the present invention is, from the viewpoint of improving the heat resistance of the resin, preferably 0.02% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, while from the same viewpoint, it is preferably 70% by mass or less, more preferably 35% by mass or less, and even more preferably 20% by mass or less.
[0101] The content of the organic solvent in the composition of the present invention is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, while it is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, even more preferably 60% by mass or less, and even more preferably 40% by mass or less. The content of each component can be calculated from the blended amount of each component.
[0102] 〔resin〕 Examples of the resin include the resins described below in embodiment F. The composition of the present invention may contain a curing agent and a curing accelerator, if necessary. The content or blending amount of the modified cellulose fiber in the composition of the present invention, more specifically in the resin composition of the present invention, is preferably 4.0 mass% or more, more preferably 5.0 mass% or more, and even more preferably 6.0 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 mass% or less, more preferably 15 mass% or less, and even more preferably 10 mass% or less.
[0103] When the composition of the present invention contains an organic solvent and a resin, the preferred contents or blending amounts of each of the components are as follows. The content or amount of cellulose fiber in the composition of the present invention, more specifically in the resin composition of the present invention, i.e., the amount of the cellulose fiber portion excluding the bound modifying group or the bound silane compound, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less.
[0104] The content or blending amount of the silane compound in the composition of the present invention, more specifically in the resin composition of the present invention, i.e., the total amount of the silane compound bonded to the modified cellulose fiber and the silane compound not bonded, is preferably 0.03 mass% or more, more preferably 0.15 mass% or more, and even more preferably 0.3 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 40 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less.
[0105] The content or blending amount of the modifying group in the composition of the present invention, more specifically in the resin composition of the present invention, is preferably 0.02 mass% or more, more preferably 0.1 mass% or more, and even more preferably 0.2 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 70 mass% or less, more preferably 35 mass% or less, and even more preferably 20 mass% or less.
[0106] The content or blending amount of the organic solvent in the composition of the present invention, more specifically in the resin composition of the present invention, is preferably 1 mass % or more, more preferably 5 mass % or more, and even more preferably 10 mass % or more, while it is preferably 49 mass % or less, more preferably 45 mass % or less, and even more preferably 40 mass % or less.
[0107] The content or blending amount of the resin in the composition of the present invention, more specifically in the resin composition of the present invention, is preferably 70 mass % or more, more preferably 75 mass % or more, and even more preferably 80 mass % or more from the viewpoint of improving the resin moldability, while it is preferably 95 mass % or less, more preferably 94 mass % or less, and even more preferably 93 mass % or less from the viewpoint of improving the heat resistance of the resin. The content of each component can be calculated from the blended amount of each component.
[0108] The mass ratio of the amount of modified cellulose fiber to the amount of resin in the composition of the present invention, more specifically in the resin composition (amount of modified cellulose fiber / amount of resin) is preferably 5 / 95 or more, more preferably 6 / 94 or more, and even more preferably 7 / 93 or more, from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 / 80 or less, more preferably 15 / 85 or less, and even more preferably 10 / 90 or less.
[0109] The mass ratio of the amount of cellulose fiber to the amount of resin in the composition of the present invention, more specifically in the resin composition (amount of cellulose fiber / amount of resin) is preferably 0.1 / 99.9 or more, more preferably 0.5 / 99.5 or more, and even more preferably 1 / 99 or more, from the viewpoint of improving the heat resistance of the resin, and from the same viewpoint, is preferably 20 / 80 or less, more preferably 10 / 90 or less, and even more preferably 5 / 95 or less. Here, the amount of cellulose fiber refers to the amount of cellulose fiber excluding the bonded modifying group and the bonded silane compound.
[0110] [Other ingredients] The composition may contain, for example, plasticizers, crystal nucleating agents, fillers (inorganic fillers, organic fillers), hydrolysis inhibitors, flame retardants, antioxidants, lubricants such as hydrocarbon waxes and anionic surfactants, ultraviolet absorbers, antistatic agents, antifogging agents, light stabilizers, pigments, antifungal agents, antibacterial agents, foaming agents, surfactants; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, glue, and casein; inorganic compounds such as tannins, zeolites, ceramics, and metal powders; fragrances; flow regulators; leveling agents; conductive agents; ultraviolet dispersion agents; and deodorants, within the scope of the present invention. Furthermore, it is also possible to add other polymeric materials and other compositions within the scope of the present invention.
[0111] E. Resin additive comprising modified cellulose fiber according to embodiment C above The resin additive of embodiment E of the present invention comprises the modified cellulose fiber described in embodiment C above, and may further comprise an organic solvent. By adding the resin additive of the present invention to a resin, the heat resistance and strength of the resin when cured can be improved.
[0112] [Organic solvent] As organic solvent it is preferable to choose the solvents described in aspect D above.
[0113] 〔composition〕 The preferred contents of the respective components in the resin additive of the present invention are the same as those in the case where the composition of the present invention contains an organic solvent. The content of each component can be calculated from the blended amount of each component.
[0114] [Other ingredients] The resin additives may contain, for example, plasticizers, crystal nucleating agents, fillers (inorganic fillers, organic fillers), hydrolysis inhibitors, flame retardants, antioxidants, lubricants such as hydrocarbon waxes and anionic surfactants, ultraviolet absorbers, antistatic agents, antifogging agents, light stabilizers, pigments, antifungal agents, antibacterial agents, foaming agents, surfactants; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, glue, and casein; inorganic compounds such as tannins, zeolites, ceramics, and metal powders; fragrances; flow regulators; leveling agents; conductive agents; ultraviolet dispersion agents; and deodorants, within the scope of the present invention. Furthermore, it is also possible to add other polymer materials and other compositions within the scope of the present invention.
[0115] F. Method for producing a resin composition comprising steps 5 and 6 One embodiment of the method for producing a resin composition of the present invention comprises: Step 5: A step of bonding a modifying group other than a silanol group to the ionic group of the cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 6: A step of mixing one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds, the cellulose fibers to which the modifying groups are bonded, and a resin. A method for producing a resin composition comprising: The method for producing a resin composition, wherein the amount of the silane compound blended in step 6 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded.
[0116] [Cellulose fibers having ionic groups] The main properties of the "cellulose fibers having ionic groups" subjected to step 5 are the same as those in embodiment A above.
[0117] [Preparation of cellulose fibers having ionic groups] The method for preparing the "cellulose fibers having ionic groups" subjected to step 5 is the same as that in embodiment A above.
[0118] [Step 5] Step 5 in the present invention is the same as step 1 in embodiment A above.
[0119] [Step 6] Step 6 in the present invention is a step of mixing a specific silane compound, i.e., one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds, the cellulose fibers having modified groups bonded thereto obtained in step 5, and a resin. It is presumed that the mixing converts at least a part of the functional groups of the silane compound into silanol groups, and at least a part of the silanol groups reacts with at least a part of the hydroxyl groups of the cellulose fibers to which the modifying groups are bonded, so that the silane compound bonds to the cellulose fibers to which the modifying groups are bonded. Therefore, the modified cellulose fibers obtained through step 6 have modifying groups and groups derived from the silane compound.
[0120] [Silane compounds] The silane compound used in this step is the same as that in the above embodiment A.
[0121] [resin] The resin used in this step is preferably a curable resin. Examples of the curable resin include a urethane resin, a (meth)acrylic resin, an epoxy resin, a urea resin, a melamine resin, and a phenolic resin. One or more resins selected from the group consisting of a urethane resin, a (meth)acrylic resin, and an epoxy resin are preferred.
[0122] When the curable resin is a urethane resin, examples of the curable monomer include aromatic isocyanates such as tolylene diisocyanate and diphenylmethane diisocyanate, aliphatic isocyanates such as hexamethylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, and tetramethyl xylylene diisocyanate, and polyols such as ethylene glycol, diethylene glycol, butanediol, hexanediol, neopentyl diol, hydroxyethyl acrylate, trimethylolpropane, dimethylolpropionic acid, and isophorone diamine. The reaction product of isocyanate and polyol becomes a urethane resin, but is not limited to this. Oligomers of the listed polyols, polyether polyols, polyester polyols, polycarbonate polyols, and other polyols may be used as the curable prepolymer.
[0123] When the curable resin is a (meth)acrylic resin, examples of the curable monomer include mono(meth)acrylates such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, n-hexyl acrylate, n-hexyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, nonanediol diacrylate, phenoxyethyl acrylate, (meth)acrylates of bisphenol A-alkylene oxide adducts, epoxy (meth)acrylates (bisphenol A type epoxy (meth)acrylate, novolac type epoxy (meth)acrylate, etc.), polyester (meth)acrylates (for example, aliphatic polyester type (meth)acrylate, aromatic polyester type (meth)acrylate, etc.), urethane (meth)acrylates (polyester type urethane (meth)acrylate, polyether type urethane (meth)acrylate, etc.), silicone (meth)acrylate, and cyanoacrylate. Oligomers of the listed mono(meth)acrylates may also be used as curable prepolymers.
[0124] When the curable resin is an epoxy resin, examples of the curable monomer include bisphenol A type, phenol novolac type, glycidyl ether type, alicyclic type, glycidyl amine type, glycidyl ester type, etc. Oligomers of the listed monomers may be used as the curable prepolymer.
[0125] When the curable resin is a urea resin, the curable monomer may be urea and formaldehyde. When the curable resin is a melamine resin, the curable monomer may be melamine and formaldehyde. When the curable resin is a phenol resin, the curable monomer may be phenol, cresol, xylenol, resorcinol, and formaldehyde.
[0126] [Hardening agents and hardening accelerators] When a thermosetting resin is used as the resin, a curing agent and / or a curing accelerator may be used.
[0127] The curing agent can be appropriately selected according to the type of resin. For example, when the resin is an epoxy resin, the curing agent may be, for example, an amine-based curing agent, a phenol resin-based curing agent, an acid anhydride-based curing agent, a polymercaptan-based curing agent, or a latent curing agent (such as boron trifluoride-amine complex, dicyandiamide, or carboxylic acid hydrazide). The curing agent may be used alone or in combination of two or more kinds. The curing agent may also act as a curing accelerator.
[0128] The ratio of the curing agent can be appropriately selected depending on the type of the curing agent, and is preferably 0.1 to 300 parts by mass, for example, relative to 100 parts by mass of the resin.
[0129] The curing accelerator can also be appropriately selected depending on the type of resin, and examples of the curing accelerator when the resin is an epoxy resin include phosphines, amines, etc. The curing accelerator may be used alone or in combination of two or more kinds.
[0130] The ratio of the curing accelerator can be appropriately selected depending on the type of curing agent, and is preferably 0.01 to 100 parts by mass, for example, relative to 100 parts by mass of the resin.
[0131] [Mixing conditions] The mixing temperature, mixing time, and solvent that can be used during mixing are the same as those in step 2. In step 6, the silane compound, cellulose fibers bonded with a modifying group, and resin may be mixed simultaneously, or the two components may be mixed first and then the remaining component may be mixed. For example, the cellulose fibers bonded with a modifying group and the resin may be mixed first, and then the silane compound may be added to the mixture and mixed. Furthermore, in order to disperse the components in step 6 more uniformly, a dispersion treatment using a high-pressure homogenizer or the like may be performed after mixing is completed.
[0132] (Silane compound content) The amount of the silane compound in step 6 is 50 parts by mass or more relative to 100 parts by mass of the cellulose fibers having modified groups bonded thereto. Here, the mass of the cellulose fibers having modified groups bonded thereto refers to the mass of only the cellulose fiber portion in the cellulose fibers having modified groups bonded thereto, i.e., the mass of the cellulose fiber portion excluding the modifying groups from the cellulose fibers having modified groups bonded thereto. From the viewpoint of improving the heat resistance of a resin when blended with the silane compound, the blending amount of the silane compound is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more. On the other hand, from the viewpoint of cost, the blending amount of the silane compound is preferably 1,000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 500 parts by mass or less.
[0133] (Resin content) From the viewpoint of improving resin moldability, the amount of resin blended in step 6 is preferably 1000 parts by mass or more, more preferably 2000 parts by mass or more, and even more preferably 5000 parts by mass or more, per 100 parts by mass of cellulose fiber to which modifying groups are bonded, while from the viewpoint of improving heat resistance, the amount of resin blended is preferably 100000 parts by mass or less, more preferably 50000 parts by mass or less, and even more preferably 10000 parts by mass or less. Here, the mass of cellulose fiber to which modifying groups are bonded refers to the mass of only the cellulose fiber portion in the cellulose fiber to which modifying groups are bonded, i.e., the mass of the cellulose fiber portion obtained by excluding the modifying groups from the cellulose fiber to which modifying groups are bonded.
[0134] [Fine-refining process and short fiber treatment] As in the above-mentioned embodiment A, a cellulose fiber finerization step and / or a cellulose fiber shortening treatment can be carried out at any stage of the production process of the present invention.
[0135] G. Method for producing a resin composition comprising steps 7 and 8 A further aspect of the method for producing a resin composition of the present invention is Step 7: mixing the cellulose fiber having an ionic group with one or more silane compounds selected from the group consisting of a chlorosilane compound, an alkoxysilane compound, an acetoxysilane compound, and a silanol compound to obtain a cellulose fiber having a silane compound bonded thereto; and Step 8: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing a resin composition comprising: The method for producing a resin composition, wherein the amount of the silane compound blended in step 7 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber having an ionic group.
[0136] [Cellulose fibers having ionic groups] The main properties of the "cellulose fibers having ionic groups" subjected to step 7 are the same as those in embodiment A above.
[0137] [Preparation of cellulose fibers having ionic groups] The method for preparing the "cellulose fibers having ionic groups" subjected to step 7 is the same as that in embodiment A above.
[0138] [Step 7] Step 7 in the present invention is the same as step 3 in embodiment B above. It is presumed that by mixing, at least a portion of the functional groups of the silane compound are converted to silanol groups, and at least a portion of these silanol groups react with at least a portion of the hydroxyl groups of the cellulose fibers having ionic groups, thereby bonding the silane compound to the cellulose fibers.
[0139] [Silane compounds] The silane compound used in this step is the same as that in the above embodiment A.
[0140] (Silane compound content) The amount of the silane compound in step 7 is 50 parts by mass or more per 100 parts by mass of the cellulose fibers having ionic groups. Here, the mass of the cellulose fibers having ionic groups refers to the mass of only the cellulose fiber portion in the cellulose fibers having ionic groups, i.e., the mass of the cellulose fiber portion excluding the ionic groups from the cellulose fibers having ionic groups. From the viewpoint of improving the heat resistance of the resin composition or the resin molded body, the amount of the silane compound is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more. On the other hand, from the viewpoint of cost, the amount of the silane compound is preferably 1,000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 500 parts by mass or less.
[0141] [Step 8] Step 7 in the present invention is the same as step 4 in embodiment B above.
[0142] [resin] The resin, curing agent and curing accelerator used in embodiment G are the same as those used in step 6 of embodiment F above. In embodiment G, the resin may be compounded in step 7 or in step 8. When the resin is blended in step 7, the mixing temperature, mixing time, and solvent that can be used in mixing are the same as those in step 6.
[0143] (Resin content) The amount of resin blended in step 7 is preferably 1000 parts by mass or more, more preferably 2000 parts by mass or more, and even more preferably 5000 parts by mass or more, per 100 parts by mass of cellulose fibers having ionic groups, from the viewpoint of improving resin moldability, while the amount of resin blended is preferably 100000 parts by mass or less, more preferably 50000 parts by mass or less, and even more preferably 10000 parts by mass or less, from the viewpoint of improving heat resistance. Here, the mass of the cellulose fibers having ionic groups refers to the mass of only the cellulose fiber portion in the cellulose fibers having ionic groups, i.e., the mass of the cellulose fiber portion obtained by removing the ionic groups from the cellulose fibers having ionic groups.
[0144] [Fine-refining process and short fiber treatment] As in the above-mentioned embodiment A, a cellulose fiber finerization step and / or a cellulose fiber shortening treatment can be carried out at any stage of the production process of the present invention.
[0145] H. Resin composition The resin composition of the present invention comprises A modified cellulose fiber obtained by bonding a cellulose fiber having a modifying group other than a silanol group to a silane compound, and resin It is a resin composition comprising:
[0146] Preferred examples of the silane compound in the resin composition of the present invention include one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds, and more specifically, the silane compounds listed in the above-mentioned "Step 2" section.
[0147] The amount of the silane compound in the resin composition of the present invention is preferably 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group other than the silanol group is bonded, from the viewpoint of improving the heat resistance of the resin composition and the resin molded product. More specifically, from the same viewpoint, the amount of the silane compound is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more, while from the viewpoint of cost, the amount of the silane compound is preferably 1000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 500 parts by mass or less.
[0148] Other details regarding the modified cellulose fiber and resin, and the amounts of each component constituting the resin composition, are as described in items A to D above.
[0149] The resin composition of the present invention can be produced, for example, by the production method of embodiment F or embodiment G described above. The resin composition produced by the above-mentioned production method of embodiment F or embodiment G contains modified cellulose fiber and a resin. The resin composition may or may not contain a solvent. At least a part of the modified cellulose fiber is bonded to the silane compound. Furthermore, an unreacted product of the silane compound or an oligomer thereof may be present in the resin composition.
[0150] In the resin composition produced by the production method of the above-mentioned embodiment F or embodiment G, the preferred contents of the respective constituent components are as follows. The content of cellulose fibers in the resin composition, i.e., the amount of the cellulose fiber portion excluding the bound modifying groups and the bound silane compounds, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less.
[0151] The content of the silane compound in the resin composition, i.e., the total amount of the silane compound bonded to the modified cellulose fiber and the silane compound not bonded, is preferably 0.03 mass% or more, more preferably 0.15 mass% or more, and even more preferably 0.3 mass% or more, from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 40 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less.
[0152] The content of the modifying group in the resin composition is, from the viewpoint of improving the heat resistance of the resin, preferably 0.02% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, while from the same viewpoint, it is preferably 70% by mass or less, more preferably 35% by mass or less, and even more preferably 20% by mass or less.
[0153] The resin content in the resin composition is preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more from the viewpoint of improving the moldability of the resin, while it is preferably 95% by mass or less, more preferably 94% by mass or less, and even more preferably 93% by mass or less from the viewpoint of improving the heat resistance of the resin. The content of each component can be calculated from the blended amount of each component.
[0154] The resin composition may or may not contain a solvent.
[0155] When the resin composition contains a solvent and a resin, the preferred contents of the respective components are as follows. The content of cellulose fibers in the resin composition, i.e., the amount of the cellulose fiber portion excluding the bound modifying groups and the bound silane compounds, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less.
[0156] The content of the silane compound in the resin composition, i.e., the total amount of the silane compound bonded to the modified cellulose fiber and the silane compound not bonded, is preferably 0.03 mass% or more, more preferably 0.15 mass% or more, and even more preferably 0.3 mass% or more, from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 40 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less.
[0157] The content of the modifying group in the resin composition is, from the viewpoint of improving the heat resistance of the resin, preferably 0.02% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, while from the same viewpoint, it is preferably 70% by mass or less, more preferably 35% by mass or less, and even more preferably 20% by mass or less.
[0158] The solvent content in the resin composition is preferably 1 mass% or more, more preferably 5 mass% or more, and even more preferably 10 mass% or more, while it is preferably 49 mass% or less, more preferably 45 mass% or less, and even more preferably 40 mass% or less.
[0159] The resin content in the resin composition is preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more from the viewpoint of improving the moldability of the resin, while it is preferably 95% by mass or less, more preferably 94% by mass or less, and even more preferably 93% by mass or less from the viewpoint of improving the heat resistance of the resin. The content of each component can be calculated from the blended amount of each component.
[0160] Preferred examples of the solvent that can be used herein include methanol, ethanol, isopropanol (IPA), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), cyclohexanone, ethyl acetate, acetonitrile, dichloromethane, chloroform, toluene, acetic acid, 1-methoxy-2-propanol (PGME), water, and the like. These can be used alone or in combination of two or more.
[0161] [Other ingredients] The resin composition may contain, for example, plasticizers, crystal nucleating agents, fillers (inorganic fillers, organic fillers), hydrolysis inhibitors, flame retardants, antioxidants, lubricants such as hydrocarbon waxes and anionic surfactants, ultraviolet absorbers, antistatic agents, antifogging agents, light stabilizers, pigments, antifungal agents, antibacterial agents, foaming agents, surfactants; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, glue, and casein; inorganic compounds such as tannins, zeolites, ceramics, and metal powders; fragrances; flow regulators; leveling agents; conductive agents; ultraviolet dispersion agents; and deodorants, within the scope of the present invention. Furthermore, it is also possible to add other polymeric materials and other compositions within the scope of the present invention.
[0162] [Resin Molded Body] A cured product such as a coating film obtained by curing the resin composition, or a resin molded product can be produced by molding the cured product. The resin molded product can be produced by appropriately using the composition of the present invention in a known molding method such as coating molding, extrusion molding, injection molding, press molding, cast molding, or solvent casting. Among these known molding methods, coating molding and cast molding are preferred from the viewpoint of productivity.
[0163] In such a resin molded product, the preferred contents of the respective constituent components are as follows. The cellulose fiber content in the resin molded body, i.e., the amount of the cellulose fiber portion excluding the bound modifying group or the bound silane compound, is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more, from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less.
[0164] The content of silane compounds in the resin molded body, i.e., the total amount of silane compounds bonded to the modified cellulose fibers and unbonded silane compounds, is preferably 0.03 mass% or more, more preferably 0.15 mass% or more, and even more preferably 0.3 mass% or more from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 40 mass% or less, more preferably 20 mass% or less, and even more preferably 10 mass% or less.
[0165] The content of the modifying group in the resin molded product is preferably 0.02% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, from the viewpoint of improving the heat resistance of the resin, while from the same viewpoint, it is preferably 70% by mass or less, more preferably 35% by mass or less, and even more preferably 20% by mass or less.
[0166] The resin content in the resin molded product is, from the viewpoint of improving the moldability of the resin, preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more, while, from the viewpoint of improving the heat resistance of the resin, it is preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 94% by mass or less, even more preferably 93% by mass or less, even more preferably 90% by mass or less, even more preferably 80% by mass or less, and even more preferably 70% by mass or less. The content of each component can be calculated from the blended amount of each component.
[0167] I. Uses of the Invention The modified cellulose fiber obtained by the production method of the present invention, the composition containing the modified cellulose fiber, the resin additive, and the resin composition obtained by the production method of the present invention can be suitably used in the following fields: Semiconductor applications, specifically, photoresists, buffer coat films, rewiring materials, backgrind tapes, dicing tapes, die bond films, epoxy sealants, film sealants, underfills, mold underfills, CMP pads, printed wiring board materials, etc. Display applications, specifically, polarizer protective films, surface treatment films, backlight films, QD sheets, protective films, transparent conductive films, cover sheets, back panels, foldable cover sheets, retardation films for circular polarizers, OLED substrates, OLED sealants, OLED bank materials, etc. Automotive applications, specifically, millimeter wave radar compatible decorative materials, LiDAR interference filters, automotive lens materials, automotive OCA / OCR, intermediate films, connector terminals, motor insulating sheets, etc. Passive component applications, specifically, aluminum electrolytic capacitors, film capacitors, multilayer ceramic capacitors, inductors, varistors, etc. Electromagnetic wave material applications, specifically, electromagnetic wave shielding, noise suppression shielding, etc. Optical material applications, specifically, light control glass and film, film for projector screens, graphite sheets, LED phosphor materials, optical fibers, etc. Heat dissipation material applications, specifically, heat dissipation metals, heat dissipation resin substrates, heat dissipation sheets, phase change sheets, heat dissipation greases, heat dissipation gap fillers, heat dissipation adhesives, etc. Transportation equipment material applications, specifically, exterior parts, engine parts, structural materials, etc. for automobiles, trains, ships, and aircraft.
[0168] In relation to the above-mentioned embodiments, the present invention further discloses the following resin composition, resin molded product, method for producing modified cellulose fiber, method for producing resin composition, and modified cellulose fiber.
[0169] <1> A modified cellulose fiber obtained by bonding a cellulose fiber having a modifying group other than a silanol group to a silane compound, and resin A resin composition comprising:
[0170] <2> The modifying group other than the silanol group is bonded to the cellulose fiber by an ionic bond and / or a covalent bond; <1> The resin composition according to claim 1. <3> The modifying group other than the silanol group is a hydrocarbon group and / or a polymer group. <1> or <2> The resin composition according to claim 1. <4> The modifying group other than the silanol group is a hydrocarbon group having 1 or more carbon atoms, preferably 3 or more, more preferably 8 or more, and even more preferably 10 or more carbon atoms, and on the other hand, preferably 30 or less, more preferably 22 or less, and even more preferably 18 or less carbon atoms. <1> ~ <3> The resin composition according to any one of claims 1 to 10. <5> the modifying group other than a silanol group is a polymer group, the molecular weight of which is preferably 100 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, even more preferably 600 or more, even more preferably 1,000 or more, even more preferably 1,500 or more, and on the other hand, preferably 10,000 or less, more preferably 7,000 or less, even more preferably 5,000 or less, even more preferably 4,000 or less, even more preferably 3,500 or less, even more preferably 2,500 or less; <1> ~ <4> The resin composition according to any one of claims 1 to 10. <6> The modifying group other than the silanol group is preferably a functional group having a repeating structure linked by a structure having an oxygen atom, more preferably a functional group having a repeating structure linked by an oxygen atom, such as a polyoxyalkylene structure (alkylene oxide chain) or a polysiloxane structure (silicone chain), even more preferably a functional group having a polyoxyalkylene structure, and even more preferably a polymer group which is an alkoxypolyoxyalkylene group. <1> ~ <5> The resin composition according to any one of claims 1 to 10. <7> The content or blending amount of the modified cellulose fiber in the resin composition is preferably 4.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 6.0% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less. <1> ~ <6> The resin composition according to any one of claims 1 to 10. <8> The content or blending amount of cellulose fiber in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. <1> ~ <7> The resin composition according to any one of claims 1 to 10. <9> The mass ratio of the amount of modified cellulose fiber to the amount of resin in the resin composition (amount of modified cellulose fiber / amount of resin) is preferably 5 / 95 or more, more preferably 6 / 94 or more, and even more preferably 7 / 93 or more, and is preferably 20 / 80 or less, more preferably 15 / 85 or less, and even more preferably 10 / 90 or less. <1> ~ <8> The resin composition according to any one of claims 1 to 10. <10> The mass ratio of the amount of cellulose fiber to the amount of resin in the resin composition (amount of cellulose fiber / amount of resin) is preferably 0.1 / 99.9 or more, more preferably 0.5 / 99.5 or more, and even more preferably 1 / 99 or more, and is preferably 20 / 80 or less, more preferably 10 / 90 or less, and even more preferably 5 / 95 or less. <1> ~ <9> The resin composition according to any one of claims 1 to 10. <11> The resin content in the resin composition is preferably 70% by mass or more, more preferably 75% by mass or more, and even more preferably 80% by mass or more, and is preferably 95% by mass or less, more preferably 94% by mass or less, and even more preferably 93% by mass or less. <1> ~ <10> The resin composition according to any one of claims 1 to 10. <12> The content or amount of modified cellulose fiber in the resin composition is preferably 4.0% by mass or more, more preferably 5.0% by mass or more, and even more preferably 6.0% by mass or more, while preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less, and the content or amount of cellulose fiber in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, while preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, and the mass ratio of the amount of modified cellulose fiber to the amount of resin in the resin composition (amount of modified cellulose fiber / amount of resin) is preferably 5 / 95 or more, and more preferably 6 / 94 or more, the mass ratio of the amount of cellulose fiber to the amount of resin in the resin composition (amount of cellulose fiber / amount of resin) is preferably 0.1 / 99.9 or more, more preferably 0.5 / 99.5 or more, even more preferably 1 / 99 or more, and preferably 20 / 80 or less, more preferably 10 / 90 or less, and the content of resin in the resin composition is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, and preferably 95% by mass or less, more preferably 94% by mass or less, and even more preferably 93% by mass or less. <1> ~ <11> The resin composition according to any one of claims 1 to 10. <13> the modifying group other than a silanol group is preferably a functional group having a (co)polymer structure of one or more oxyalkylenes selected from oxyalkylenes having a carbon number of 2 to 8, more preferably a (co)polymer structure of one or more oxyalkylenes selected from oxyalkylenes having a carbon number of 2 to 4, even more preferably a (co)polymer structure of one or two oxyalkylenes selected from ethylene oxide (EO) and propylene oxide (PO), and even more preferably a polyoxyalkylene structure which is a copolymer structure (also referred to as an (EO / PO) structure) in which ethylene oxide (EO) and propylene oxide (PO) are polymerized randomly or in a block form; <1> ~ <12> The resin composition according to any one of claims 1 to 10. <14> Step 1: A step of bonding a modifying group other than a silanol group to an ionic group of a cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 2: mixing the cellulose fiber having the modifying group bonded thereto with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. A method for producing modified cellulose fibers comprising: A method for producing modified cellulose fibers, wherein the amount of the silane compound blended in step 2 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded. <15> Step 3: mixing cellulose fibers having ionic groups with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds to obtain cellulose fibers having silane compounds bonded thereto; and Step 4: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing modified cellulose fibers comprising: A method for producing a modified cellulose fiber, wherein the amount of the silane compound blended in step 3 is 50 parts by mass or more per 100 parts by mass of a cellulose fiber portion of the cellulose fiber having an ionic group. <16> Step 5: A step of bonding a modifying group other than a silanol group to the ionic group of the cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 6: A step of mixing one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds, the cellulose fibers to which the modifying groups are bonded, and a resin. A method for producing a resin composition comprising: The method for producing a resin composition, wherein the amount of the silane compound blended in step 6 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded. <17> Step 7: mixing the cellulose fiber having an ionic group with one or more silane compounds selected from the group consisting of a chlorosilane compound, an alkoxysilane compound, an acetoxysilane compound, and a silanol compound to obtain a cellulose fiber having a silane compound bonded thereto; and Step 8: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing a resin composition comprising: The method for producing a resin composition, wherein the amount of the silane compound blended in step 7 is 50 parts by mass or more per 100 parts by mass of a cellulose fiber portion of the cellulose fiber having an ionic group. <18> The modifying group other than the silanol group is bonded to the cellulose fiber by an ionic bond and / or a covalent bond; <14> ~ <17> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <19> The modifying group other than the silanol group is a hydrocarbon group and / or a polymer group. <14> ~ <18> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <20> The modifying group other than the silanol group is a hydrocarbon group having 1 or more carbon atoms, preferably 3 or more, more preferably 8 or more, and even more preferably 10 or more carbon atoms, and on the other hand, preferably 30 or less, more preferably 22 or less, and even more preferably 18 or less carbon atoms. <14> ~ <19> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <21> the modifying group other than a silanol group is a polymer group, the molecular weight of which is preferably 100 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, even more preferably 600 or more, even more preferably 1,000 or more, even more preferably 1,500 or more, and on the other hand, preferably 10,000 or less, more preferably 7,000 or less, even more preferably 5,000 or less, even more preferably 4,000 or less, even more preferably 3,500 or less, even more preferably 2,500 or less; <14> ~ <20> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <22> The modifying group other than the silanol group is preferably a functional group having a repeating structure linked by a structure having an oxygen atom, more preferably a functional group having a repeating structure linked by an oxygen atom such as a polyoxyalkylene structure (alkylene oxide chain) or a polysiloxane structure (silicone chain), further preferably a functional group having a polyoxyalkylene structure, and further preferably an alkoxypolyoxyalkylene group. <14> ~ <21> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <23> the modifying group other than a silanol group is preferably a functional group having a (co)polymer structure of one or more oxyalkylenes selected from oxyalkylenes having a carbon number of 2 to 8, more preferably a (co)polymer structure of one or more oxyalkylenes selected from oxyalkylenes having a carbon number of 2 to 4, even more preferably a (co)polymer structure of one or two oxyalkylenes selected from ethylene oxide (EO) and propylene oxide (PO), and even more preferably a polyoxyalkylene structure which is a copolymer structure (also referred to as an (EO / PO) structure) in which ethylene oxide (EO) and propylene oxide (PO) are polymerized randomly or in a block form; <14> ~ <22> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <24> The modifying compound is preferably a compound having a modifying group and a cationic group, more preferably a compound having a modifying group and an amino group or a quaternary ammonium group. <14> ~ <23> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <25> The amount of the modifying compound used in step 1 is preferably 0.10 equivalents or more, more preferably 0.15 equivalents or more, and even more preferably 0.2 equivalents or more, and is preferably 20 equivalents or less, more preferably 5 equivalents or less, more preferably 1 equivalent or less, and even more preferably 0.7 equivalents or less. <14> ~ <24> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <26> The crystallinity of the cellulose fiber having an ionic group is preferably 10% or more, more preferably 15% or more, even more preferably 20% or more, even more preferably 30% or more, even more preferably 40% or more, even more preferably 50% or more, and on the other hand, is preferably 90% or less, more preferably 85% or less, even more preferably 80% or less. <14> ~ <25> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <27> The average fiber diameter of the cellulose fibers to which the modifying group is bonded is preferably 1 nm or more, more preferably 2 nm or more, and is preferably 300 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 120 nm or less. <14> ~ <26> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <28> The average fiber length of the cellulose fibers to which the modifying group is bonded is preferably 10 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more, and is preferably 1000 nm or less, more preferably 500 nm or less, and even more preferably 300 nm or less. <14> ~ <27> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <29> The amount of the modifying group bound to the cellulose fiber is preferably 0.01 mmol / g or more, and is preferably 3.0 mmol / g or less. <14> ~ <28> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <30> The temperature during mixing, i.e., the reaction temperature, is preferably 70° C. or lower, more preferably 50° C. or lower, and even more preferably 30° C. or lower, and is preferably −20° C. or higher, more preferably −10° C. or higher, and preferably −5° C. or higher. <14> ~ <29> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <31> The mixing time is preferably 0.1 hours or more, more preferably 0.5 hours or more, and even more preferably 1 hour or more, and is preferably 120 hours or less, more preferably 72 hours or less, more preferably 48 hours or less, and even more preferably 24 hours or less. <14> ~ <30> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <32> The amount of the silane compound is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more, and is preferably 1000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 500 parts by mass or less. <14> ~ <31> 1. A method for producing a modified cellulose fiber or a method for producing a resin composition according to any one of claims 1 to 9. <33> The above <14> ~ <32> A modified cellulose fiber produced by the method for producing a modified cellulose fiber according to any one of claims 1 to 5. <34> The above <1> ~ <13> 13. A resin molded product comprising the resin composition according to claim 12. EXAMPLES
[0171] The present invention will be specifically described below with reference to examples. Note that the following examples are merely illustrative of the present invention and do not imply any limitation. Note that "normal pressure" refers to 101.3 kPa, and "normal temperature" refers to 25°C.
[0172] [Average fiber diameter and average fiber length of (shortened) anionically modified cellulose fibers] Deionized water was added to the cellulose fiber to be measured or a suspension containing the cellulose fiber to be measured to prepare a dispersion with a content of 0.01% by mass. The dispersion was measured using a wet dispersion type image analysis particle size distribution meter (manufactured by Jusco International, product name: IF-3200) under the following conditions: front lens: 2x, telecentric zoom lens: 1x, image resolution: 0.835 μm / pixel, syringe inner diameter: 6515 μm, spacer thickness: 500 μm, image recognition mode: ghost, threshold: 8, analysis sample amount: 1 mL, sampling: 15%. The length of the short axis of the cellulose fiber when it is approximated as a rectangle is taken as the fiber diameter, and the length of the long axis is taken as the fiber length. The respective values were measured for 100 cellulose fibers, and the average values were calculated.
[0173] [Average fiber diameter and average fiber length of cellulose fibers after micronization treatment] Deionized water was added to the cellulose fiber to be measured or the dispersion containing the cellulose fiber to be measured to prepare a dispersion with a content of 1% by mass. After adjusting the pH to 9 with sodium hydroxide, a high-pressure homogenizer (Yoshida Kikai Kogyo Co., Ltd., Nanovaita L-ES) was used for five times dispersion treatment at 150 MPa. Deionized water was added so that the content of cellulose fiber in the dispersion was 0.01% by mass. The dispersion was dropped onto mica, and the water droplets were removed with air and dried as an observation sample, and the measurement was performed in dynamic force mode using an atomic force microscope (AFM) (Hitachi High-Tech Corporation, AFM-5100N; the probe used was Hitachi High-Tech Corporation, SI-DF20P2). At that time, 100 or more cellulose fibers were extracted from the microscope image in which the cellulose fiber could be confirmed, and the average fiber diameter was calculated from the fiber height. The average fiber length was calculated from the distance in the fiber direction.
[0174] [Carboxy group content in TEMPO oxidized cellulose fiber] A 100 mL beaker is filled with 0.5 g of cellulose fiber to be measured, and ion-exchanged water or a 2 / 1 mixed solvent of methanol and water is added to make a total of 55 mL. 5 mL of 0.01 M aqueous sodium chloride solution is added to the beaker to prepare a dispersion. The dispersion is stirred until the cellulose fiber to be measured is sufficiently dispersed. 0.1 M hydrochloric acid is added to the dispersion to adjust the pH to 2.5 to 3, and an automatic titration device (manufactured by DKK-TOA Corporation, product name "AUT-701") is used to drop 0.05 M aqueous sodium hydroxide solution into the dispersion with a waiting time of 60 seconds, and the conductivity and pH value are measured every minute. The measurement is continued until the pH reaches about 11, and a conductivity curve is obtained. The sodium hydroxide titration amount is determined from the conductivity curve, and the anionic group content of the cellulose fiber to be measured is calculated using the following formula.
[0175] Carboxylic group content (mmol / g) = sodium hydroxide titration amount × sodium hydroxide aqueous solution concentration (0.05M) / mass of cellulose fiber to be measured (0.5g)
[0176] [Content of each ingredient] The content of each component other than water was calculated from the blended amount of each component. The water content in the dispersion or suspension was measured by Karl Fischer titration using a Mitsubishi Analytech CA-200. The solid content of each type of cellulose fiber was calculated by measuring the moisture content in the sample using an infrared moisture meter (Shimadzu Corporation, MOC-120H) and calculating the difference from 100% by mass. The moisture content was measured every 30 seconds at a constant temperature of 150°C for 1 g of sample, and the value displayed when the mass loss in 30 seconds was 0.1% or less was used.
[0177] [Measurement of electrical conductivity of filtrate] The electrical conductivity of the filtrate was measured using a compact electrical conductivity meter (HORIBA, Ltd., LAQUAtwin EC-33B).
[0178] [Measurement of the average polymerization degree of anionically modified cellulose fibers] The average degree of polymerization of the anionically modified cellulose fiber was measured as follows. (1) Preparation of measurement solutions 0.06 g of anion-modified cellulose fiber to be measured was precisely weighed (dry mass) and placed in a 50 mL beaker, and water was added so that the solid content concentration was 1% by mass. 0.006 g of sodium borohydride was added and stirred at room temperature for 2 hours, after which 18 g of acetone was added, and then centrifuged at 10 ° C, 10,000 G, and 1 minute using a high-speed cooling centrifuge (Koki Holdings Co., Ltd., CR21G III) to remove the supernatant. 18 g of ethanol was added to the residue, and the process of centrifuging and removing the supernatant was repeated three times to obtain a precipitate washed with ethanol. The obtained precipitate was vacuum-dried at 40 ° C for 12 hours to obtain reduced pulp in which the aldehyde groups in the anion-modified cellulose fiber were reduced. 15 mL of deionized water and 15 mL of 1 M copper ethylenediamine solution were added to 0.06 g of the obtained reduced pulp, and the mixture was stirred at room temperature for 1 hour to obtain a measurement solution.
[0179] (2) Measurement of average degree of polymerization The measurement solution obtained in (1) above was placed in an Ubbelohde viscometer and allowed to stand in a thermostatic bath (20±0.1)°C for 1 hour. The flow time of the liquid (t (seconds)) and the flow time of the copper ethylenediamine solution without added cellulose (t0 (seconds)) were then measured, and the intrinsic viscosity [η] (dL / g) was calculated using the following formula.
[0180] [η]=[(t / t0-1) / c] / [1+0.28×(t / t0-1)] (c: Cellulose concentration (g / dL))
[0181] From the obtained intrinsic viscosity [η], the average degree of polymerization (DP) of the anion-modified cellulose fiber was calculated using the following formula: v ) was calculated.
[0182] [η] = 0.094 × 162 × DP v 0.67
[0183] [Amount of modified groups bonded and introduction rate of modified groups in various cellulose fibers] The amount of modified groups bonded is determined by the following IR measurement method, and the amount of bonded and the introduction rate are calculated according to the following formula: For example, when a modified group is bonded to a TEMPO-oxidized cellulose fiber, IR measurement is performed by measuring dried TEMPO-oxidized cellulose fiber or a cellulose fiber bonded with a modified group by the ATR method using an infrared absorption spectrometer (IR) (manufactured by Thermo Fisher Scientific, trade name: Nicolet 6700), and the amount of bonded modified group and the introduction rate are calculated according to the following formulas A and B.
[0184] <Formula A> Amount of modified group bound (mmol / g) = a × (bc) ÷ d a: Carboxylic group content of TEMPO oxidized cellulose fiber (mmol / g) b: TEMPO oxidized cellulose fiber 1720 cm -1 Peak intensity of c: 1720 cm of cellulose fiber with modified groups -1 Peak intensity of d: TEMPO oxidized cellulose fiber 1720 cm -1 Peak intensity of 1720cm -1 Peak intensity: Peak intensity derived from the carbonyl group of carboxylic acid
[0185] <Formula B> Modification group introduction rate (mol%) = 100 × e / f e: Amount of modified group bound (mmol / g) f: Carboxylic group content of TEMPO-oxidized cellulose fiber (mmol / g)
[0186] [Cellulose fiber content (equivalent amount) of various cellulose fibers] The cellulose fiber amount (equivalent amount) in various cellulose fibers is the amount of only the cellulose fiber in the various cellulose fibers excluding the modifying group. In the modified cellulose fibers of the present invention, the formula weight of the modifying group may be considerably larger (for example, larger than the molecular weight of glucose), so in this specification, when it is appropriate to explain the modified cellulose fibers without considering the difference in the formula weight of the modifying group, the amount (equivalent amount) of the cellulose fiber constituting the modified cellulose fiber is expressed instead of the amount of the modified cellulose fiber.
[0187] The amount of cellulose fiber (converted amount) is measured by the following method. (a) When one type of "modifying compound" is added The amount of cellulose fiber (equivalent amount) is calculated by the following formula E. <Formula E>: Amount of cellulose fiber (equivalent amount) (g) = Mass of cellulose fiber to which a modifying group is bonded (g) / [1 + molecular weight of modifying compound (g / mol) × amount of modified group bonded (mmol / g) × 0.001] (b) When two or more types of "modifying compounds" are added The amount of cellulose fiber (converted amount) is calculated taking into consideration the molar ratio of each compound (that is, the molar ratio when the total molar amount of the modifying compounds to be added is taken as 1).
[0188] [Confirmation of crystal structures in various cellulose fibers] The crystal structures of various cellulose fibers, such as raw cellulose fiber, cellulose fiber having an ionic group, and modified cellulose fiber, are confirmed by measurement under the following conditions using a diffractometer (manufactured by Rigaku Corporation, product name: MiniFlexII). Measurement pellet preparation conditions: A pellet press was applied to the freeze-dried cellulose fiber in the range of 10 to 20 MPa to produce pellets with an area of 320 mm. 2 Prepare a smooth pellet with a thickness of ×1 mm. X-ray diffraction analysis conditions: step angle 0.01°, scan speed 10° / min, measurement range: diffraction angle 2θ=5~40° X-ray source: Cu / Kα-radiation, tube voltage: 15kv, tube current: 30mA Peak splitting conditions: After removing background noise, perform fitting with a Gaussian function so that the error between 2θ=13-23° is within 5%.
[0189] The crystal structures of various cellulose fibers are confirmed by measuring them using the above-mentioned diffractometer under the above-mentioned conditions. The degree of crystallinity of the cellulose type I crystal structure is calculated based on the following formula (A) using the area of the X-ray diffraction peak obtained by the above-mentioned peak division. Cellulose type I crystallinity (%) = [I cr / (I cr +I am )]×100 (A) [In the formula, I cr is the area of the diffraction peak of the lattice plane (002 plane) (diffraction angle 2θ = 22-23°) in X-ray diffraction, I am indicates the area of the diffraction peak of the amorphous part (diffraction angle 2θ = 18.5°).
[0190] Preparation Example 1 (Preparation of Short Anion-Modified Cellulose Fiber) [Anion-modified cellulose fiber] Anion-modified cellulose fibers having the physical properties shown in Table 1 were used as raw materials.
[0191] [Table 1]
[0192] Such anionically modified cellulose fibers can be prepared, for example, by the TEMPO oxidation treatment described below.
[0193] [TEMPO oxidation treatment] In a 2L PP beaker equipped with a mechanical stirrer and stirring blades, 10 g of bleached coniferous kraft pulp fiber as the raw material natural cellulose fiber and 990 g of deionized water are weighed and stirred at 25°C and 100 rpm for 30 minutes. Next, 0.13 g of 2,2,6,6-tetramethyl-1-piperidine-N-oxyl (TEMPO), 1.3 g of sodium bromide, and 35.5 g of 10.5 mass% sodium hypochlorite aqueous solution are added in this order to 10 g of the pulp fiber. Next, pH stat titration is performed using an automatic titration device, and 0.5 M sodium hydroxide aqueous solution is dropped to maintain the pH at 10.5. The reaction is carried out at a stirring speed of 100 rpm and 25°C for 120 minutes. Next, 0.01 M hydrochloric acid is added thereto while stirring to make the pH of the suspension 2. Next, the solid content is filtered out by suction filtration. The solids are dispersed in deionized water and filtered off by suction filtration. This operation is repeated until the conductivity of the filtrate is 200 μS / cm or less. The resulting solids are then dehydrated to obtain anion-modified cellulose fibers.
[0194] [Preparation of short anion-modified cellulose fibers] Anion-modified cellulose fibers having the physical properties shown in Table 1 were subjected to alkaline hydrolysis and hot water treatment to prepare shortened anion-modified cellulose fibers having the physical properties shown in Table 2. In this manner, cellulose fibers having carboxy groups as ionic groups were prepared.
[0195] [Table 2]
[0196] Such shortened anionically modified cellulose fibers can be prepared, for example, by the following alkaline hydrolysis treatment and hot water treatment.
[0197] [Alkaline hydrolysis treatment] A suspension of anion-modified cellulose fibers with a solid content of 144.5 g and the physical properties shown in Table 1 is diluted with 1000 g of deionized water, to which 1.4 g of 35% hydrogen peroxide solution (1 part by mass of hydrogen peroxide per 100 parts by mass of the solid content of the raw cellulose fibers) is added, and the pH is adjusted to 12 with 1 M aqueous sodium hydroxide solution. Then, an alkaline hydrolysis treatment is performed for 2 hours at 80°C (solid content concentration of the suspension of anion-modified cellulose fibers is 4.3% by mass). After cooling the suspension to room temperature, 0.01 M hydrochloric acid is added to adjust the pH of the suspension to 2. The solid content is filtered out from the suspension by suction filtration.
[0198] [Hot water treatment] The solid content obtained by the alkaline hydrolysis treatment is dispersed in deionized water, and the solid content is separated by suction filtration. This operation is repeated until the conductivity of the filtrate becomes 200 μS / cm or less. Deionized water is added to the suspension so that the solid content concentration in the suspension becomes 5 mass%, and the suspension is stirred at 95° C. for 12 hours, and then cooled to room temperature to obtain an aqueous suspension of shortened anion-modified cellulose fibers. The aqueous suspension obtained is centrifuged to obtain shortened anion-modified cellulose fibers. The physical properties of the shortened anion-modified cellulose fibers after micronization treatment were an average fiber diameter of 3.9 nm and an average fiber length of 130 nm.
[0199] Preparation Example 2 (Preparation of a composition containing cellulose fiber 1 having a modifying group bonded thereto and a resin) Short fiber anion-modified cellulose fibers having the physical properties shown in Table 2 were added to 1-methoxy-2-propanol (PGME) to obtain a dispersion with a solids concentration of 2.0 mass%. 4.1 g of EO / PO amine was added to 300 g of the obtained dispersion, and the mixture was stirred at 25°C for 1 hour to obtain a dispersion of cellulose fibers to which modifying groups were bonded. The amount of EO / PO amine used as the modifying compound was 0.26 equivalents relative to the ionic groups, i.e., carboxy groups, of the short fiber anion-modified cellulose fibers.
[0200] 300 g of epoxy resin was further added to the obtained dispersion of cellulose fibers having modified groups bonded thereto, and after stirring at 25°C for 1 hour, dispersion treatment was carried out five times at 150 MPa using a high-pressure homogenizer (Nano Vaita L-ES, manufactured by Yoshida Kikai Kogyo Co., Ltd.). Then, PGME was removed from the dispersion of cellulose fibers having modified groups bonded thereto using an evaporator, to obtain a composition containing cellulose fibers 1 having modified groups bonded thereto and a resin. The obtained composition was liquid at room temperature.
[0201] Preparation Example 3 (Preparation of a composition containing cellulose fiber 2 having a modifying group bonded thereto and a resin) Short fiber anion-modified cellulose fibers having the physical properties shown in Table 2 were added to 1-methoxy-2-propanol (PGME) to obtain a dispersion with a solid content concentration of 2.0 mass%. 1.4 g of trioctylamine was added to 300 g of the obtained dispersion, and the mixture was stirred at 25°C for 1 hour to obtain a dispersion of cellulose fibers to which a modifying group was bonded. Here, the amount of trioctylamine used as a modifying compound was 0.5 equivalents relative to the ionic group, i.e., the carboxy group, of the short fiber anion-modified cellulose fibers.
[0202] 300 g of epoxy resin was further added to the obtained dispersion of cellulose fibers having modified groups bonded thereto, and after stirring at 25°C for 1 hour, dispersion treatment was carried out five times at 150 MPa using a high-pressure homogenizer (Nanovater L-ES, manufactured by Yoshida Kikai Kogyo Co., Ltd.). Then, PGME was removed from the dispersion of cellulose fibers having modified groups bonded thereto using an evaporator, thereby obtaining a composition containing cellulose fibers 2 having modified groups bonded thereto and a resin. The obtained composition was liquid at room temperature.
[0203] Example 1 (Composition containing modified cellulose fibers and resin) 0.2 g of a curing agent and 0.12 g of a curing accelerator were added to 4 g of the composition obtained in Preparation Example 2 (containing 0.13 g of cellulose fiber 1 to which a modifying group was bonded (the mass of the cellulose fiber portion obtained by removing the modifying group from the cellulose fiber to which a modifying group was bonded is 0.08 g) and 3.87 g of resin), and the mixture was stirred at 25 ° C. and 2000 rpm for 10 minutes and degassed at 25 ° C. and 2200 rpm for 2 minutes using an automatic revolution type mixer (Thinky Corporation, Awatori Rentaro). Then, 0.048 g of 3-aminopropyltrimethoxysilane, a silane compound, was added, and the mixture was stirred at 25 ° C. and 2000 rpm for 5 minutes and degassed at 25 ° C. and 2200 rpm for 2 minutes using an automatic revolution type mixer (Thinky Corporation, Awatori Rentaro), to obtain the composition shown in Table 3.
[0204] Example 2 The composition shown in Table 3 was obtained by carrying out the same process as in Example 1 above, except that the amount of the silane compound added was changed to 0.16 g.
[0205] Example 3 The composition shown in Table 4 was obtained by carrying out the same process as in Example 1 above, except that the silane compound was changed to N-phenyl-3-aminopropyltrimethoxysilane and the amount added was changed to 0.16 g.
[0206] Example 4 The composition shown in Table 4 was obtained by carrying out the same process as in Example 1 above, except that the silane compound was changed to n-propyltrimethoxysilane and the amount added was changed to 0.16 g.
[0207] Example 5 0.2 g of a curing agent and 0.12 g of a curing accelerator were added to 3.97 g of the composition obtained in Preparation Example 3 (containing 0.10 g of cellulose fiber 2 to which a modifying group was bonded (the mass of the cellulose fiber portion obtained by removing the modifying group from the cellulose fiber to which a modifying group was bonded is 0.08 g) and 3.87 g of resin), and the mixture was stirred at 25 ° C. and 2000 rpm for 10 minutes using an automatic revolution type mixer (Thinky Corporation, Awatori Rentaro), and degassed at 25 ° C. and 2200 rpm for 2 minutes. Thereafter, 0.16 g of 3-aminopropyltrimethoxysilane, a silane compound, was added, and the mixture was stirred at 25 ° C. and 2000 rpm for 5 minutes using an automatic revolution type mixer (Thinky Corporation, Awatori Rentaro), and degassed at 25 ° C. and 2200 rpm for 2 minutes to obtain the composition shown in Table 4.
[0208] Comparative Example 1 and Comparative Example 2 The compositions shown in Table 3 were obtained by carrying out the same process as in Example 1 above, except that the amount of the silane compound added was changed to 0 g (Comparative Example 1) or 0.016 g (Comparative Example 2).
[0209] Comparative Example 3 Short fiber anion-modified cellulose fibers having the physical properties shown in Table 2, that is, cellulose fibers having ionic groups, were added to PGME to obtain a dispersion having a solid content concentration of 2.0 mass %.
[0210] 300g of epoxy resin was added to 300g of the obtained dispersion, and after stirring at 25℃ for 1 hour, dispersion treatment was carried out 5 times at 150MPa using a high-pressure homogenizer (Nanovaita L-ES, manufactured by Yoshida Kikai Kogyo Co., Ltd.) The obtained cellulose fiber dispersion aggregated and settled immediately after the dispersion treatment, so it was not possible to produce a resin film.
[0211] Comparative Example 4 The composition shown in Table 4 was obtained by carrying out the same process as in Example 5 above, except that no silane compound was used.
[0212] Reference example 1 The composition shown in Table 3 was obtained by carrying out the same process as in Example 1 above, except that the cellulose fiber was not used.
[0213] Test Example 1 (Evaluation of Dispersibility) The dispersibility of the cellulose fibers having modified groups bonded thereto was evaluated as follows. For Examples 1 and 2 and Comparative Examples 1 and 2, the "PGME dispersion of cellulose fibers bonded with modification groups" obtained as an intermediate product in Preparation Example 2 was used as the evaluation subject, and for Comparative Example 3, the "PGME dispersion of short fiber anion-modified cellulose fibers" prepared as an intermediate product was used as the evaluation subject. Each was left to stand at room temperature for 1 day, visually inspected for the occurrence of precipitates, and evaluated based on the following evaluation criteria. If the evaluation result was A or B, the dispersibility was determined to be good, and if the evaluation result was A, the dispersibility was determined to be better.
[0214] A: No precipitate was formed. B: Some precipitation was confirmed. F: The liquid components and solids have completely separated, and the entire amount of solids has settled. nt: Not evaluated.
[0215] Test Example 2 (Evaluation of Resin Film) [Preparation of resin film] The composition containing the modified cellulose fiber and resin obtained in each example was applied to copper foil with a coating thickness of 170 μm using an applicator (manufactured by Tester Sangyo Co., Ltd.), and then heated at 130°C for 2 hours to harden the composition, thereby producing a resin film.
[0216] [Measurement of storage modulus] The resin film was peeled off from the copper foil, and a rectangular sample measuring 5 mm wide and 40 mm long was cut out. Using a dynamic viscoelasticity device (manufactured by SII, "DMS6100"), the storage modulus of the sample was measured in a tensile mode in a nitrogen atmosphere, at a frequency of 1 Hz, by increasing the temperature from 30°C to 300°C at a rate of 10°C per minute, with a chuck distance of 20 mm. The storage modulus values used were those at 30°C and 200°C.
[0217] The storage modulus (E') shown in Tables 3 and 4 is a value at 30° C. or 200° C., and is expressed in GPa. The higher this value, the better the strength, and therefore the higher the storage modulus at high temperatures, the better the heat resistance.
[0218] [Measurement of glass transition temperature (Tg)] The resin film was peeled off from the copper foil, and a rectangular sample measuring 5 mm in width and 20 mm in length was cut out. Using a dynamic viscoelasticity device (manufactured by SII, "DMS6100"), measurements were taken in a tensile mode under a nitrogen atmosphere, at a frequency of 1 Hz, with the temperature rising from 30°C to 300°C at a rate of 10°C per minute. The glass transition point (Tg) was determined using the temperature at the peak top of tan δ. A higher glass transition temperature (°C) indicates better heat resistance.
[0219] [Table 3]
[0220] [Table 4]
[0221] In Tables 3 and 4, "amount of silane compound blended relative to CNF" refers to the number of parts by mass of (blended) silane compound per 100 parts by mass of the cellulose fiber (CNF) portion of the cellulose fiber to which a modifying group is bonded.
[0222] Details of the main components used in the above examples are as follows: [resin] Epoxy resin (Mitsubishi Chemical Corporation, jER828, epoxy equivalent = 184-194, weight average molecular weight = 370) [Hardening agent] Dicyandiamide (DICY, manufactured by Mitsubishi Chemical Corporation) was ground using a mini blender (manufactured by Osaka Chemical Co., Ltd.) and used. [Cure accelerator] 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) (manufactured by Thermo Scientific) was ground using a mini blender (manufactured by Osaka Chemical Co., Ltd.) and used. [Silane compounds] 3-Aminopropyltrimethoxysilane (abbreviated as "amino" in the table) (manufactured by Shin-Etsu Silicone Co., Ltd., KBM-903) n-Propyltrimethoxysilane (abbreviated as "propyl" in the table) (manufactured by Shin-Etsu Silicone Co., Ltd., KBM-3033) N-phenyl-3-aminopropyltrimethoxysilane (abbreviated as "N-phenyl" in the table) (manufactured by Shin-Etsu Silicones Co., Ltd., KBM-573) [others] PGME: 1-methoxy-2-propanol (manufactured by Daicel Corporation) EO / PO amine: methoxypoly(oxyethylene / oxypropylene)-2-propylamine (HUNTSMAN, Jeffamine M2070, Mw=2000, EO:PO=4:1) [Industrial Applicability]
[0223] The modified cellulose fiber of the present invention can be used in various molded products fields such as home appliance parts, electronics, aerospace, civil engineering and construction, automobiles, and vehicle-mounted applications.
Claims
1. A modified cellulose fiber obtained by bonding a cellulose fiber having a modifying group other than a silanol group to a silane compound, and resin A resin composition comprising:
2. The resin composition according to claim 1, wherein the silane compound is one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds.
3. The resin composition according to claim 1 , wherein the amount of the silane compound is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group other than the silanol group is bonded.
4. The resin composition according to claim 1, wherein the amount of the modified cellulose in the resin composition is 4.0% by mass or more and 20% by mass or less.
5. The resin composition according to claim 1 , wherein the amount of the resin in the resin composition is 70% by mass or more and 95% by mass or less.
6. A resin molded product comprising the resin composition according to claim 1 or 2.
7. Step 1: A step of bonding a modifying group other than a silanol group to an ionic group of a cellulose fiber having an ionic group to obtain a cellulose fiber having the modifying group bonded thereto; and Step 2: A step of mixing the cellulose fiber having the modifying group bonded thereto with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds. A method for producing modified cellulose fibers comprising: A method for producing modified cellulose fibers, wherein the amount of the silane compound in step 2 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the cellulose fiber to which the modifying group is bonded.
8. Step 3: mixing cellulose fibers having ionic groups with one or more silane compounds selected from the group consisting of chlorosilane compounds, alkoxysilane compounds, acetoxysilane compounds, and silanol compounds to obtain cellulose fibers having silane compounds bonded thereto; and Step 4: A step of obtaining modified cellulose fibers by bonding a modifying group other than a silanol group to the ionic group of the cellulose fibers to which the silane compound is bonded. A method for producing modified cellulose fibers comprising: A method for producing a modified cellulose fiber, wherein the amount of the silane compound blended in step 3 is 50 parts by mass or more per 100 parts by mass of the cellulose fiber portion of the ionic group-containing cellulose fiber.
Citation Information
Patent Citations
Fiber-reinforced composite material and method for production thereof and precursor for producing fiber-reinforced composite material
JP2006241450A